The OCEAN ICE mooring compilation: a standardised, pan-Antarctic database of ocean hydrography and current time series - Zhou, S.; Dutrieux, P.; Giulivi, C. F.; Jenkins, A.; Silvano, A.; Auckland, C.; Abrahamsen, E. P.; Meredith, M.; Vaňková, I.; Nicholls, K.; Davis, P. E. D.; Østerhus, S.; et al. (Earth Syst. Sci. Data, 2025)
Continuous moored time series of temperature, salinity, pressure and current speed and direction are of great importance for understanding the continental shelf and under-ice-shelf dynamics and thermodynamics that govern water mass transformations and ice melting in and around Antarctic marginal seas. In these regions, icebergs and sea ice make ship-based mooring deployment and recovery challenging. Nevertheless, over decades, expeditions around the fringe of Antarctica sporadically deployed and recovered hundreds of moored instruments, including those facilitated through ice shelves boreholes. These datasets tend to be archived in a wide range of data centres, with, to our knowledge, no clear format standardisation. As a result, systematic analysis of historical mooring time series in the marginal seas is often challenging. Here we present the first version of a standardised pan-Antarctic moored hydrography and current time series compilation, with broad international contributions from data centres, research institutes and individual data owners. The mooring records in this compilation span over five decades, from the 1970s to the 2020s, providing an opportunity for a systematic study of the pan-Antarctic water mass transport and shelf connectivity. As a demonstration of the utility of this compilation, we present spectral analysis of the compiled current velocity time series, which unsurprisingly shows the dominating presence of tidal variability within most records. This component of the variability is fitted using multi-linear regression to tidal frequencies, and the tidal fit is removed from the original time series to leave de-tided variability. Given the limited record durations to months to years, de-tided variability is dominated by synoptic (3–10 d period), intraseasonal (10–80 d) and seasonal (∼6 months–1 year) signals. The spatial distribution of the kinetic energy integrated within frequency bands is presented and discussed within respective regional contexts, and future avenues of research are proposed. This data compilation is assembled under the endorsement of Ocean-Cryosphere Exchanges in ANtarctica: Impacts on Climate and the Earth System (OCEAN ICE) project (https://ocean-ice.eu/, last access: 23 October 2025) funded by the European Commission and UK Research and Innovation. It is available and regularly updated in NetCDF format with the SEANOE database at https://doi.org/10.17882/99922 (Zhou et al., 2024a).
Keywords: Sørishavet; database; geofysikk; hydrografi; oseanografi

Bedmap3 updated ice bed, surface and thickness gridded datasets for Antarctica - Pritchard, Hamish D.; Fretwell, Peter T.; Fremand, Alice C.; Bodart, Julien A.; Kirkham, James D.; Aitken, Alan; Bamber, Jonathan; Bell, Robin; Bianchi, Cesidio; Bingham, Robert G.; Blankenship, Donald D.; Casassa, Gino; et al. (Scientific Data, 2025)
We present Bedmap3, the latest suite of gridded products describing surface elevation, ice-thickness and the seafloor and subglacial bed elevation of the Antarctic south of 60 °S. Bedmap3 incorporates and adds to all post-1950s datasets previously used for Bedmap2, including 84 new aero-geophysical surveys by 15 data providers, an additional 52 million data points and 1.9 million line-kilometres of measurement. These efforts have filled notable gaps including in major mountain ranges and the deep interior of East Antarctica, along West Antarctic coastlines and on the Antarctic Peninsula. Our new Bedmap3/RINGS grounding line similarly consolidates multiple recent mappings into a single, spatially coherent feature. Combined with updated maps of surface topography, ice shelf thickness, rock outcrops and bathymetry, Bedmap3 reveals in much greater detail the subglacial landscape and distribution of Antarctica’s ice, providing new opportunities to interpret continental-scale landscape evolution and to model the past and future evolution of the Antarctic ice sheets.
Keywords: Antarktis; geofysikk; geomorfologi; glasiologi; hydrologi; oseanografi

ALBATROSS: Advancing Southern Ocean tide modelling with high resolution and enhanced bathymetry - Le Merle, Eva; Belot, Carole; Fouchet, Ergane; Cancet, Mathilde; Andersen, Ole Baltazar; Lyard, Florent; Moholdt, Geir; Tsamados, Michel; El Hajj, Mahmoud; Maton, Josephine; Benveniste, Jérôme; Restano, Marco (Polar Science, 2024)
The knowledge of bathymetry and ocean tides plays a pivotal role at the crossroads of various scientific fields, especially in the Polar regions. Its significance extends to ocean circulation modeling and understanding the coupled dynamical response of the ocean, sea-ice and ice-sheet systems. In the Southern Ocean, conventional satellite altimetry measurements are rare below the 66° parallel. Hydrodynamic models are thus useful tools to provide spatially continuous information about ocean tides. However, the accuracy of ocean tide models around the Antarctic continent is currently limited by the quality of bathymetry. Recent reprocessing of decade-long CryoSat-2 data has facilitated a new computation of bathymetry around Antarctica, bringing innovative information on bathymetry gradients. This, combined with new compilations of bathymetry, ice draft, coastline, and grounding line datasets in ice-shelf regions, allows improving models and knowledge of ocean tides in the Southern Ocean. We developed a new high-resolution tidal model that implements the improved bathymetry data and includes data assimilation of satellite-altimetry tidal retrievals computed from CryoSat-2, filling the gap between the 66°S-limited coverage of the TOPEX-Jason suite missions and the Antarctic coast. Comparisons with tidal estimates derived from tide gauge measurements showed very good consistencies with an RMSE of 3 cm.
Keywords: Sørishavet; batymetri; geofysikk

Gross Primary Production of Antarctic Landfast Sea Ice: A Model-Based Estimate - Wongpan, Pat; Meiners, K. M.; Vancoppenolle, M.; Fraser, A. D.; Moreau, Sebastien; Saenz, B. T.; Swadling, K. M.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2024)
Much of the Antarctic coast is covered by seasonal landfast sea ice (fast ice), which serves as an important habitat for ice algae. Fast-ice algae provide a key early season food source for pelagic and benthic food webs, and contribute to biogeochemical cycling in Antarctic coastal ecosystems. Summertime fast ice is undergoing a decline, leading to more seasonal fast ice with unknown impacts on interconnected Earth system processes. Our understanding of the spatiotemporal variability of Antarctic fast ice, and its impact on polar ecosystems is currently limited. Evaluating the overall productivity of fast-ice algae has historically been hampered by limitations in observations and models. By linking new fast-ice extent maps with a one-dimensional sea-ice biogeochemical model, we provide the first estimate of the spatio-seasonal variability of Antarctic fast-ice algal gross primary production (GPP) and its annual primary production on a circum-Antarctic scale. Experiments conducted for the 2005?2006 season provide a mean fast ice-algal production estimate of 2.8 Tg C/y. This estimate represents about 12% of overall Southern Ocean sea-ice algae production (estimated in a previous study), with the mean fast-ice algal production per area being 3.3 times higher than that of pack ice. Our Antarctic fast-ice GPP estimates are probably underestimated in the Ross Sea and Weddell Sea sectors because the sub-ice platelet layer habitats and their high biomass are not considered.
Keywords: Sørishavet; alger; biogeokjemi; geofysikk; havis; oseanografi; sjøis

Antarctic permafrost degassing in Taylor Valley by extensive soil gas investigation - Ruggiero, L.; Sciarra, A.; Mazzini, A.; Florindo, F.; Wilson, G.; Tartarello, M.C.; Mazzoli, C.; Anderson, J.T.H.; Romano, V.; Worthington, R.; Bigi, S.; Sassi, R.; et al. (Science of The Total Environment, 2023)
Ongoing studies conducted in northern polar regions reveal that permafrost stability plays a key role in the modern carbon cycle as it potentially stores considerable quantities of greenhouse gases. Rapid and recent warming of the Arctic permafrost is resulting in significant greenhouse gas emissions, both from physical and microbial processes. The potential impact of greenhouse gas release from the Antarctic region has not, to date, been investigated. In Antarctica, the McMurdo Dry Valleys comprise 10 % of the ice-free soil surface areas in Antarctica and like the northern polar regions are also warming albeit at a slower rate. The work presented herein examines a comprehensive sample suite of soil gas (e.g., CO2, CH4 and He) concentrations and CO2 flux measurements conducted in Taylor Valley during austral summer 2019/2020. Analytical results reveal the presence of significant concentrations of CO2, CH4 and He (up to 3.44 vol%, 18,447 ppmv and 6.49 ppmv, respectively) at the base of the active layer. When compared with the few previously obtained measurements, we observe increased CO2 flux rates (estimated CO2 emissions in the study area of 21.6 km2 ≈ 15 tons day−1). We suggest that the gas source is connected with the deep brines migrating from inland (potentially from beneath the Antarctic Ice Sheet) towards the coast beneath the permafrost layer. These data provide a baseline for future investigations aimed at monitoring the changing rate of greenhouse gas emissions from Antarctic permafrost, and the potential origin of gases, as the southern polar region warms.
Keywords: Antarktis; drivhusgasser; geofysikk; geologi; geostatistikk; isbreer; permafrost

Synthesis of field and satellite data to elucidate recent mass balance of five ice rises in Dronning Maud Land, Antarctica - Goel, Vikram; Morris, Ashley; Moholdt, Geir; Matsuoka, Kenichi (Frontiers in Earth Science, 2022)
We investigated mass balance changes over five ice rises in the last few decades near Fimbul and Nivl ice shelves in central Dronning Maud Land. We use the Input-Output Method constrained using field-based geophysical measurements conducted during the austral summers of 2012–14 over three ice rises near the Fimbul Ice Shelf. Further, we use satellite altimetry data (ICESat, ICESat-2, and CryoSat-2) to estimate geodetic mass balance over all five ice rises in recent decades. Both field- and satellite-based estimates show that until 2010, three out of five ice rises were thickening (0.4–0.2 mieq a−1) while two were close to balance. However, over the last decade, the ice rises thickening previously started to thin (−0.2–−0.6 mieq a−1) while the other two remained close to balance. Much of this variability is likely associated with regional surface mass balance trends, with each ice rise exhibiting its characteristics depending on its local glaciological settings.
Keywords: Dronning Maud Land; geofysikk; glasiologi

Evaluation of Temperature-Dependent Complex Refractive Indices of Supercooled Liquid Water Using Downwelling Radiance and In-Situ Cloud Measurements at South Pole - Rowe, Penny M; Walden, Von P; Brandt, Richard E; Town, Michael S; Hudson, Stephen R; Neshyba, Steven (Journal of Geophysical Research: Atmospheres, 2022)
Clouds have a large effect on the radiation budget and represent a major source of uncertainty in climate models. Supercooled liquid clouds can exist at temperatures as low as 235 K, and the radiative effect of these clouds depends on the complex refractive index (CRI) of liquid water. Laboratory measurements have demonstrated that the liquid-water CRI is temperature-dependent, but corroboration with field measurements is difficult. Here we present measurements of the downwelling infrared radiance and in-situ measurements of supercooled liquid water in a cloud at temperatures as low as 240 K, made at South Pole Station in 2001. These results demonstrate that including the temperature dependence of the liquid-water CRI is essential for accurate calculations of radiative transfer through supercooled liquid clouds. Furthermore, we show that when cloud properties are retrieved from infrared radiances (using the spectral range 500–1,200 cm−1) spurious ice may be retrieved if the 300 K CRI is used for cold liquid clouds (∼240 K). These results have implications for radiative transfer in climate models as well as for retrievals of cloud properties from infrared radiance spectra.
Keywords: Antarktis; Sydpolen; atmosfæren; geofysikk; klimamodeller

Evaluation of Three Numerical Weather Prediction Models for the Weddell Sea Region for the Austral Winter 2013 - Jonassen, Marius O; Nygård, Tiina; Vihma, Timo (Journal of Geophysical Research: Atmospheres, 2021)
It is widely recognized that numerical weather prediction (NWP) results for the Antarctic are relatively poor compared to the mid-latitudes. In this study, we evaluate output from three operational NWP systems: the ECMWF, Global Forecast System (GFS) and Antarctic Mesoscale Prediction System (AMPS), for the Austral winter (June-August) of 2013 for the Weddell Sea region, paying special attention to regional patterns of error statistics. This is the first evaluation of NWP systems over the Southern Ocean that also addresses the accuracy of forecasted vertical profiles. In the evaluation, we use data from land- and ship-based automatic weather stations (AWS) and radiosoundings. While the ECMWF and AMPS forecasts are on average biased cold and dry near the surface, the GFS forecasts are on average biased warm and moist. The near-surface wind speed is on average overestimated by the AMPS forecasts, whereas it is slightly underestimated by the forecasts of the other two NWP systems. Among the variables investigated, all three NWP systems forecast the near-surface specific humidity most accurately, followed by the temperature and then the wind speed. The forecast quality for the near-surface and upper-air wind speed degrades the most rapidly with increasing lead time, compared to the other variables. ECMWF is the overall best NWP system when compared against both the near-surface and upper-air observations, followed by AMPS and then GFS. The generally poorest model performance is found in locations with complex terrain along the coast of the Antarctic continent, and the best over the ocean.
Keywords: Sørishavet; Weddellhavet; geofysikk; meteorologi

Case Study of Blowing Snow Impacts on the Antarctic Peninsula Lower Atmosphere and Surface Simulated With a Snow/Ice Enhanced WRF Model - Luo, Liping; Zhang, Jing; Hock, Regine; Yao, Yao (Journal of Geophysical Research: Atmospheres, 2021)
To better capture the air-snow-ice interaction, a snow/ice enhanced Weather Research and Forecasting (WRF-ice) model has been developed. This study examines the performance of WRF-ice and its blowing snow component during a strong cyclone event from October 23 to 27, 2017 over the Antarctic Peninsula, which is characterized by a synoptic cyclone crossing the northern part of the Peninsula and an embodied mesoscale cyclone over the Weddell Sea. Evolution of the cyclone is accurately reproduced in the 5-km resolution WRF-ice simulation, and the simulated near-surface conditions agree well with station and satellite observations. Numerical simulations show that the process of blowing snow sublimation can be prominent within the lower atmosphere when the air is dry, and produces moistening and cooling effects. Over relatively warm and humid areas, cloud enhancement by blowing snow can lead to either colder or warmer surfaces because of competing effects of longwave and shortwave cloud radiative forcings. In particular, additional moisture from blowing snow sublimation can slightly intensify precipitation over the mountains. Surface energy budget analysis indicates that absorbed shortwave (Sa), incoming longwave (Ld), and outgoing longwave (Lu) are dominant components of surface energy budget. When increases in Ld, Lu, and sensible heat flux are combined with decreases in Sa and latent heat flux due to blowing snow effects, a negative surface net heat flux (∼0.5 W/m2) occurs during daytime. A positive domain-total surface mass balance (∼0.43 Gt) is generated during the simulated cyclone event due to increases in precipitation, decreases in runoff, and decreases in sublimation.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; geovitenskap; is; meteorologi; polarområdene; satellite; snø

Cancellation of the Precessional Cycle in δ18O Records During the Early Pleistocene - Morée, Anne L; Sun, Tianyi; Bretones, Anaïs; Straume, Eivind O; Nisancioglu, Kerim; Gebbie, Geoffrey (Geophysical Research Letters, 2021)
The dominant pacing of glacial-interglacial cycles in deep-ocean δ18O records changed substantially during the Mid-Pleistocene Transition. The precessional cycle (∼23 ky) is absent during the Early Pleistocene, which we show can be explained by cancellation of the hemispherically antiphased precessional cycle in the Early Pleistocene interior ocean. Such cancellation develops due to mixing of North Atlantic and Southern Ocean δ18O signals at depth, and shows characteristic spatial patterns. We explore the cancellation potential for different North Atlantic and Southern Ocean deep-water source δ18O values using a tracer transport ocean model. Cancellation of precession occurs for all signal strengths and is widespread for a signal strength typical for the Early Pleistocene. Early Pleistocene precessional power is therefore likely incompletely archived in deep-sea δ18O records, concealing the true periodicity of the glacial cycles in the two hemispheres.
Keywords: Sørishavet; geofysikk; innlandsis; oseanografi; paleontologi; polarområdene

Linking Sub-Tropical Evaporation and Extreme Precipitation Over East Antarctica: An Atmospheric River Case Study - Terpstra, Annick; Gorodetskaya, Irina V; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2021)
We investigate an intense snowfall event between 15 and 18 February 2011 over the East Antarctic coastal region which contributed to roughly 24% of the annual snow accumulation. The event was previously associated with an atmospheric river, and here we use both Eulerian and Lagrangian analysis to gain an understanding of the processes contributing to the atmospheric river signature. The planetary-scale configuration during the event consisted of a persistent blocking situation resulting in a sustained meridional flow from the sub-tropics to the Antarctic ice sheet between 20 and 50°E. Within this configuration, synoptic-scale cyclogenesis contributed to slantwise ascent of moisture loaded air parcels toward Antarctica. Landfall of this cyclone’s warm sector coincided with the onset of Antarctic precipitation. Subsequently, a secondary cyclone developed along a pre-existing baroclinic zone. The rapid intensification and propagation speed of this mesoscale cyclone alongside the warm, moist air mass resulted in strong moisture flux convergence ahead of the cyclone, providing additional poleward moisture transport. The poleward progression of warm moist air and a corresponding decrease of sea-surface temperatures implied downward surface sensible and latent heat fluxes throughout the region of intense poleward moisture, roughly between 40 and 60°S. Hence, moisture uptake via surface evaporation was suppressed between the sub-tropics and the polar continent, favoring long-range transport. Identification of the surface moisture uptake region by tracing changes in moisture in air parcels confirmed the limited uptake of moisture during the poleward transport in this case study, with the primary moisture source for Antarctic precipitation located in the sub-tropics.
Keywords: Antarktis; akkumulasjon; atmosfæren; geofysikk; meteorologi; nedbør; snøfall

Atmospheric and Oceanographic Signatures in the Ice Shelf Channel Morphology of Roi Baudouin Ice Shelf, East Antarctica, Inferred From Radar Data - Drews, Reinhard; Schannwell, Clemens; Ehlers, Todd A; Gladstone, Rupert; Pattyn, Frank; Matsuoka, Kenichi (Journal of Geophysical Research: Earth Surface, 2020)
Ice shelves around Antarctica can provide back stress for outlet glaciers and control ice sheet mass loss. They often contain narrow bands of thin ice termed ice shelf channels. Ice shelf channel morphology can be interpreted through surface depressions and exhibits junctions and deflections from flowlines. Using ice flow modeling and radar, we investigate ice shelf channels in the Roi Baudouin Ice Shelf. These are aligned obliquely to the prevailing easterly winds. In the shallow radar stratigraphy, syncline and anticline stacks occur beneath the upwind and downwind side, respectively. The structures are horizontally and vertically coherent, except near an ice shelf channel junction where patterns change structurally with depth. Deeper layers truncate near basal incisions. Using ice flow modeling, we show that the stratigraphy is ∼9 times more sensitive to atmospheric variability than to oceanic variability. This is due to the continual adjustment toward flotation. We propose that syncline-anticline pairs in the shallow stratigraphy are caused by preferential snow deposition on the windward side and wind erosion at the downwind side. This drives downwind deflection of ice shelf channels of several meters per year. The depth variable structures indicate formation of an ice shelf channel junction by basal melting. We conclude that many ice shelf channels are seeded at the grounding line. Their morphology farther seaward is shaped on different length scales by ice dynamics, the ocean, and the atmosphere. These processes act on finer (subkilometer) scales than are captured by most ice, atmosphere, and ocean models, yet the dynamics of ice shelf channels may have broader implications for ice shelf stability.
Keywords: Sørishavet; brehylle; geofysikk; glasiologi; innlandsis; isbrem; isshelf

The Role of Tides in Ocean-Ice Shelf Interactions in the Southwestern Weddell Sea - Hausmann, Ute; Sallée, Jean-Baptiste; Jourdain, Nicolas; Mathiot, Pierre; Rousset, Clément; Madec, Gurvan; Deshayes, Julie; Hattermann, Tore (Journal of Geophysical Research: Oceans, 2020)
To investigate the role of tides in Weddell Sea ocean-ice shelf melt interactions, and resulting consequences for ocean properties and sea ice interactions, we develop a regional ocean-sea ice model configuration, with time-varying ocean boundary and atmospheric forcing, including the deep open ocean (at 2.5–4 km horizontal resolution), the southwestern continental shelf (≈2.5 km), and the adjacent cavities of eastern Weddell, Larsen, and Filchner-Ronne ice shelves (FRIS, 1.5–2.5 km). Simulated circulation, water mass, and ice shelf melt properties compare overall well with available open ocean and cavity observational knowledge. Tides are shown to enhance the kinetic energy of the time-varying flow in contact with the ice shelves, thereby increasing melt. This dynamically driven impact of tides on net melting is to almost 90% compensated by cooling through the meltwater that is produced but not quickly exported from regions of melting in the Weddell Sea cold-cavity regime. The resulting systematic tide-driven enhancement of both produced meltwater and its refreezing on ascending branches of, especially the FRIS, cavity circulation acts to increase net ice shelf melting (by 50% in respect to the state without tides, ≈50 Gt yr−1). In addition, tides also increase the melt-induced FRIS cavity circulation, and the meltwater export by the FRIS outflow. Simulations suggest attendant changes on the open-ocean southwestern continental shelf, characterized by overall freshening and small year-round sea ice thickening, as well as in the deep southwestern Weddell Sea in the form of a marked freshening of newly formed bottom waters.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; havis; isbrem; isshelf; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis; tidevann

Will Climate Change Impact Polar NOx Produced by Energetic Particle Precipitation? - Maliniemi, Ville; Marsh R., Daniel; Tyssøy, Hilde Nesse; Smith-Johnsen, Christine (Geophysical Research Letters, 2020)
Energetic electron precipitation (EEP) is an important source of polar nitrogen oxides (NOx) in the upper atmosphere. During winter, mesospheric NOx has a long chemical lifetime and is transported to the stratosphere by the mean meridional circulation. Climate change is expected to accelerate this circulation and therefore increase polar mesospheric descent rates. We investigate the Southern Hemispheric polar NOx distribution during the 21st century under a variety of future scenarios using simulations of the Whole Atmosphere Community Climate Model (WACCM). We simulate stronger polar mesospheric descent in all future scenarios that increase the atmospheric radiative forcing. Polar NOx in the upper stratosphere is significantly enhanced in two future scenarios with the largest increase in radiative forcing. This indicates that the ozone depleting NOx cycle will become more important in the future, especially if stratospheric chlorine species decline. Thus, EEP-related atmospheric effects may become more prominent in the future.
Keywords: Antarktis; geofysikk; klimaendringer; klimatologi; ozonlaget; polarområdene; romvitenskap

Exceptionally Warm and Prolonged Flow of Warm Deep Water Toward the Filchner-Ronne Ice Shelf in 2017 - Ryan, Svenja; Hellmer, Hartmut H; Janout, Markus; Darelius, Elin; Vignes, Lucie; Schröder, Michael (Geophysical Research Letters, 2020)
The Filchner-Ronne Ice Shelf, fringing the southern Weddell Sea, is Antarctica's second largest ice shelf. At present, basal melt rates are low due to active dense water formation; however, model projections suggest a drastic increase in the future due to enhanced inflow of open-ocean warm water. Mooring observations from 2014 to 2016 along the eastern flank of the Filchner Trough (76°S) revealed a distinct seasonal cycle with inflow if Warm Deep Water during summer and autumn. Here we present extended time series showing an exceptionally warm and long inflow in 2017, with maximum temperatures exceeding 0.5°C. Warm temperatures persisted throughout winter, associated with a fresh anomaly, which lead to a change in stratification over the shelf, favoring an earlier inflow in the following summer. We suggest that the fresh anomaly developed upstream after anomalous summer sea ice melting and contributed to a shoaling of the shelf break thermocline.
Keywords: Sørishavet; Weddellhavet; batymetri; brehylle; geofysikk; havis; isbrem; kontinentalsokkel; oseanografi; sjøis; smelting

Microcontinents and Continental Fragments Associated With Subduction Systems - van den Broek, Joost M; Gaina, Carmen (Tectonics, 2020)
Microcontinents and continental fragments are small pieces of continental crust that are surrounded by oceanic lithosphere. Although classically associated with passive margin formation, here we present several preserved microcontinents and continental fragments associated with subduction systems. They are located in the Coral Sea, South China Sea, central Mediterranean and Scotia Sea regions, and a “proto-microcontinent,” in the Gulf of California. Reviewing the tectonic history of each region and interpreting a variety of geophysical data allows us to identify parameters controlling the formation of microcontinents and continental fragments in subduction settings. All these tectonic blocks experienced long, complex tectonic histories with an important role for developing inherited structures. They tend to form in back-arc locations and separate from their parent continent by oblique or rotational kinematics. The separated continental pieces and associated marginal basins are generally small and their formation is quick (<50 Myr). Microcontinents and continental fragments formed close to large continental masses tend to form faster than those created in systems bordered by large oceanic plates. A common triggering mechanism for their formation is difficult to identify, but seems to be linked with rapid changes of complex subduction dynamics. The young ages of all contemporary pieces found in situ suggest that microcontinents and continental fragments in these settings are short lived. Although presently the amount of in-situ subduction-related microcontinents is meager (an area of 0.56% and 0.28% of global, non-cratonic, continental crustal area and crustal volume, respectively), through time microcontinents contributed to terrane amalgamation and larger continent formation.
Keywords: Sørishavet; batymetri; geofysikk; geologi; geovitenskap; litosfæren; tektonikk

Warm Circumpolar Deep Water at the Western Getz Ice Shelf Front, Antarctica - Assmann, Karen; Darelius, Elin Maria K; Wåhlin, Anna K; Kim, Tae Wan; Lee, Sang Hoon (Geophysical Research Letters, 2019)
The Getz Ice Shelf is one of the largest sources of fresh water from ice shelf basal melt in Antarctica. We present new observations from three moorings west of Siple Island 2016–2018. All moorings show a persistent flow of modified Circumpolar Deep Water toward the western Getz Ice Shelf. Unmodified Circumpolar Deep Water with temperatures up to 1.5 °C reaches the ice shelf front in frequent episodes. These represent the warmest water observed at any ice shelf front in the Amundsen Sea. Mean currents within the warm bottom layer of 18–20 cm/s imply an advection time scale of 7 days from shelf break to ice shelf front. Zonal wind stress at the shelf break affects heat content at the ice shelf front on weekly to monthly time scales. Our 2-year mooring records also evince that upwelling over the shelf break controls thermocline depth on subannual to annual time scales.
Keywords: Antarktis; geofysikk; glasiologi; isbrem; isshelf; observasjoner

Assessment of Atmospheric Reanalyses With Independent Observations in the Weddell Sea, the Antarctic - Jonassen, Marius O; Välisuo, Ilona; Vihma, Timo; Uotila, Petteri; Makshtas, Alexander P; Launiainen, Jouko (Journal of Geophysical Research: Atmospheres, 2019)
Surface layer and upper-air in situ observations from two research vessel cruises and an ice station in the Weddell Sea from 1992 and 1996 are used to validate four current atmospheric reanalysis products: ERA-Interim, CFSR, JRA-55, and MERRA-2. Three of the observation data sets were not available for assimilation, providing a rare opportunity to validate the reanalyses in the otherwise datasparse region of the Antarctic against independent data. All four reanalyses produce 2 m temperatures warmer than the observations, and the biases vary from +2.0 K in CFSR to +2.8 K in MERRA-2. All four reanalyses are generally too warm also higher up in the atmospheric boundary layer (ABL), with biases up to +1.4 K (ERA-Interim). Cloud fractions are relatively poorly reproduced by the reanalyses, MERRA-2 and JRA-55 having the strongest positive and negative biases of about +30 % and −17 %, respectively. Skill scores of the error statistics reveal that ERA-Interim compares generally the most favorably against both the surface layer and the upper-air observations. CFSR compares the second best and JRA-55 and MERRA-2 have the least favorable scores. The ABL warm bias is consistent with previous evaluation studies in high latitudes, where more recent observations have been applied. As the amount of observations has varied depending on the decade, season, and region, the consistency of the warm bias suggests a need to improve the modeling systems, including data assimilation as well as ABL and surface parameterizations.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; meteorologi; observasjoner

Quantarctica 3 released - Matsuoka, Kenichi; Skoglund, Anders; Roth, George; Melvær, Yngve; Tronstad, Stein (Fram forum, 2019)
Keywords: Antarktis; geofysikk; geografi; glasiologi; innlandsis; kartografi; satellite bilder

A note on digital elevation model smoothing and driving stresses - McCormack, Felicity S; Roberts, Jason L; Jong, Lenneke M; Young, Duncan A; Beem, Lucas H (Polar Research, 2019)
Ice-flow fields, including the driving stress, provide important information on the current state and evolution of Antarctic and Greenland ice-sheet dynamics. However, computation of flow fields from continent-scale DEMs requires the use of smoothing functions and scales, the choice of which can be ad hoc. This study evaluates smoothing functions and scales for robust calculations of driving stress from Antarctic DEMs. Our approach compares a variety of filters and scales for their capacity to minimize the residual between predicted and observed flow direction fields. We find that a spatially varying triangular filter with a width of 8–10 ice thicknesses provides the closest match between the observed and predicted flow direction fields. We use the predicted flow direction fields to highlight artefacts in observed Antarctic velocities, demonstrating that comparison of multiple observational data sets has utility for quality control of continent-scale data sets.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis; isbreer; istykkelse

Influence of Summer Sublimation on δD, δ18O, and δ17O in Precipitation, East Antarctica, and Implications for Climate Reconstruction From Ice Cores - Pang, Hongxi; Hou, Shugui; Landais, Amaelle; Masson-Delmotte, Valérie; Jouzel, Jean; Steen-Larsen, Hans Christian; Risi, Camille; Zhang, Wangbin; Wu, Shuangye; Li, Yuansheng; An, Chunlei; Wang, Yetang; et al. (Journal of Geophysical Research: Atmospheres, 2019)
In central Antarctica, where accumulation rates are very low, summer sublimation of surface snow is a key element of the surface mass balance, but its fingerprint in isotopic composition of water (δD, δ18O, and δ17O) remains unclear. In this study, we examined the influence of summer sublimation on δD, δ18O, and δ17O in precipitation using data sets of isotopic composition of precipitation at various sites on the inland East Antarctica. We found unexpectedly low δ18O values in the summer precipitation, decoupled from surface air temperatures. This feature can be explained by the combined effects of weak or nonexistent temperature inversion and moisture recycling associated with sublimation-condensation processes in summer. Isotopic fractionation during the moisture-recycling process also explains the observed high values of d-excess and 17O-excess in summer precipitation. Our results suggest that the local cycle of sublimation-condensation in summer is an important process for the isotopic composition of surface snow, water vapor, and consequently precipitation on inland East Antarctica.
Keywords: Antarktis; geofysikk; iskjerner; paleoklimatologi; stabile isotoper

Subglacial Geology and Geomorphology of the Pensacola-Pole Basin, East Antarctica - Paxman, Guy J G; Jamieson, Stewart S R; Ferraccioli, Fausto; Jordan, Tom A; Bentley, Michael J; Ross, Neil; Forsberg, René; Matsuoka, Kenichi; Steinhage, Daniel; Eagles, Graeme; Casal, Tania G (Geochemistry, Geophysics, Geosystems, 2019)
The East Antarctic Ice Sheet (EAIS) is underlain by a series of low-lying subglacial sedimentary basins. The extent, geology, and basal topography of these sedimentary basins are important boundary conditions governing the dynamics of the overlying ice sheet. This is particularly pertinent for basins close to the grounding line wherein the EAIS is grounded below sea level and therefore potentially vulnerable to rapid retreat. Here we analyze newly acquired airborne geophysical data over the Pensacola-Pole Basin (PPB), a previously unexplored sector of the EAIS. Using a combination of gravity and magnetic and ice-penetrating radar data, we present the first detailed subglacial sedimentary basin model for the PPB. Radar data reveal that the PPB is defined by a topographic depression situated ~500 m below sea level. Gravity and magnetic depth-to-source modeling indicate that the southern part of the basin is underlain by a sedimentary succession 2–3 km thick. This is interpreted as an equivalent of the Beacon Supergroup and associated Ferrar dolerites that are exposed along the margin of East Antarctica. However, we find that similar rocks appear to be largely absent from the northern part of the basin, close to the present-day grounding line. In addition, the eastern margin of the basin is characterized by a major geological boundary and a system of overdeepened subglacial troughs. We suggest that these characteristics of the basin may reflect the behavior of past ice sheets and/or exert an influence on the present-day dynamics of the overlying EAIS.
Keywords: Antarktis; Sydpolen; Sørpolen; geofysikk; geomorfologi; glasiologi; innlandsis; subglasial geologi; subglasial topografi

SuperDARN Radar-Derived HF Radio Attenuation During the September 2017 Solar Proton Events - Bland, Emma C; Heino, Erkka; Kosch, Michael J; Partamies, Noora (Space Weather, 2018)
Two solar proton events in September 2017 had a significant impact on the operation of the Super Dual Auroral Radar Network (SuperDARN), a global network of high-frequency (HF) radars designed for observing F region ionospheric plasma convection. Strong polar cap absorption caused near-total loss of radar backscatter, which prevented the primary SuperDARN data products from being determined for a period of several days. During this interval, the high-latitude and polar cap radars measured unusually low levels of background atmospheric radio noise. We demonstrate that these background noise measurements can be used to observe the spatial and temporal evolution of the polar cap absorption region, using an approach similar to riometry. We find that the temporal evolution of the SuperDARN radar-derived HF attenuation closely follows that of the cosmic noise absorption measured by a riometer. Attenuation of the atmospheric noise up to 10 dB at 12 MHz is measured within the northern polar cap, and up to 14 dB in the southern polar cap, which is consistent with the observed backscatter loss. Additionally, periods of enhanced attenuation lasting 2–4 hr are detected by the midlatitude radars in response to M- and X-class solar flares. Our results demonstrate that SuperDARN's routine measurements of atmospheric radio noise can be used to monitor 8- to 20-MHz radio attenuation from middle to polar latitudes, which may be used to supplement riometer data and also to investigate the causes of SuperDARN backscatter loss during space weather events.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; ionosfæren; polarområdene; radiostøy

Basal Settings Control Fast Ice Flow in the Recovery/Slessor/Bailey Region, East Antarctica - Diez, Anja; Matsuoka, Kenichi; Ferraccioli, Fausto; Jordan, Tom A; Corr, Hugh F; Kohler, Jack; Olesen, Arne V; Forsberg, René (Geophysical Research Letters, 2018)
The region of Recovery Glacier, Slessor Glacier, and Bailey Ice Stream, East Antarctica, has remained poorly explored, despite representing the largest potential contributor to future global sea level rise on a centennial to millennial time scale. Here we use new airborne radar data to improve knowledge about the bed topography and investigate controls of fast ice flow. Recovery Glacier is underlain by an 800 km long trough. Its fast flow is controlled by subglacial water in its upstream and topography in its downstream region. Fast flow of Slessor Glacier is controlled by the presence of subglacial water on a rough crystalline bed. Past ice flow of adjacent Recovery and Slessor Glaciers was likely connected via the newly discovered Recovery-Slessor Gate. Changes in direction and speed of past fast flow likely occurred for upstream parts of Recovery Glacier and between Slessor Glacier and Bailey Ice Stream. Similar changes could also reoccur here in the future.
Keywords: Antarktis; geofysikk; geologi; glasiologi; havnivåstigning; isbre; isstrøm

Fracture propagation and stability of ice shelves governed by ice shelf heterogeneity - Borstad, Chris; McGrath, Daniel; Pope, Allen (Geophysical Research Letters, 2017)
Tabular iceberg calving and ice shelf retreat occurs after full-thickness fractures, known as rifts, propagate across an ice shelf. A quickly evolving rift signals a threat to the stability of Larsen C, the Antarctic Peninsula's largest ice shelf. Here we reveal the influence of ice shelf heterogeneity on the growth of this rift, with implications that challenge existing notions of ice shelf stability. Most of the rift extension has occurred in bursts after overcoming the resistance of suture zones that bind together neighboring glacier inflows. We model the stresses in the ice shelf to determine potential rift trajectories. Calving perturbations to ice flow will likely reach the grounding line. The stability of Larsen C may hinge on a single suture zone that stabilizes numerous upstream rifts. Elevated fracture toughness of suture zones may be the most important property that allows ice shelves to modulate Antarctica's contribution to sea level rise.
Keywords: Antarktis; geofysikk; glasiologi; havnivåstigning; is; isberg; isbrem; isfjell; isshelf; kalv; kalving

On the effect of topography and wind on warm water inflow—An idealized study of the southern Weddell Sea continental shelf system - Daae, Kjersti; Hattermann, Tore; Darelius, Elin; Fer, Ilker (Journal of Geophysical Research: Oceans, 2017)
An idealized eddy-resolving numerical model, with topographic features common to the southern Weddell Sea, is constructed to study mechanisms through which warm deep water enters a wide continental shelf with a trough. The open ocean, represented by a 1700 m deep channel, is connected to a 400 m deep shelf with a continental slope. The shelf is narrow (50 km) in the east but widens to 300 km at the center of the model domain. Over the narrow shelf, the slope front is balanced by wind-driven Ekman downwelling and counteracting eddy overturning, favoring on-shelf transport of warm water in summer scenarios when fresher surface water is present. Over the wide shelf, the Ekman downwelling ceases, and the mesoscale eddies relax the front. Inflow of warm water is sensitive to along-shelf salinity gradients and is most efficient when denser water over the wide shelf favors up-slope eddy transport along isopycnals of the V-shaped slope front. Inflow along the eastern side of the trough cannot penetrate the sill region due to potential vorticity constraints, while along the western trough flank, eddy-induced inflow crosses the sill and reaches the ice front. The warm inflow into the trough is sensitive to the density of the outflowing dense shelf water. For weaker winds, absence of the dense water outflow leads to a reversal of the trough circulation and a strong inflow of warm water, while for stronger winds, baroclinic effects become less important and the inflow is similar to experiments including dense water outflow.
Keywords: Sørishavet; Weddellhavet; batymetri; geofysikk; havstrømmer; hydrografi; klimamodeller; klimatologi; kontinentalsokkel; vannvirvler

Exploring the Recovery Lakes region and interior Dronning Maud Land, East Antarctica, with airborne gravity, magnetic and radar measurements - Forsberg, Rene; Olesen, Arne; Jordan, Tom; Matsuoka, Kenny; Zakrajsek, Andres; Ghidella, Marta; Greenbaum, Jamin (Geological Society, London, Special Publications, 2017)
Long-range airborne geophysical measurements were carried out in the ICEGRAV campaigns, covering hitherto unexplored parts of interior East Antarctica and part of the Antarctic Peninsula. The airborne surveys provided a regional coverage of gravity, magnetic and icepenetrating radar measurements for major Dronning Maud Land ice stream systems, from the grounding lines up to the Recovery Lakes drainage basin, and filled in major data voids in Antarctic data compilations, such as AntGP for gravity data, ADMAP for magnetic data and BEDMAP2 for ice thickness data and the sub-ice topography. We present the first maps of gravity, magnetic and ice thickness data and bedrock topography for the region and show examples of bedrock topography and basal reflectivity patterns. The 2013 Recovery Lakes campaign was carried out with a British Antarctic Survey Twin Otter aircraft operating from the Halley and Belgrano II stations, as well as a remote field camp located at the Recovery subglacial Lake B site. Gravity measurements were the primary driver for the survey, with two airborne gravimeters (Lacoste and Romberg and Chekan-AM) providing measurements at an accuracy level of around 2 mGal r.m.s., supplementing GOCE (Gravity Field and Steady-State Ocean Circulation Explorer) satellite data and confirming an excellent sub-milligal agreement between satellite and airborne data at longer wavelengths.
Keywords: Dronning Maud Land; geofysikk; glasiologi

Volcanic passive continental margin beneath Maitri station in central DML, East Antarctica: constraints from crustal shear velocity through receiver function modelling - Gupta, Sandeep; Kanna, Nagaraju; Akilan, A (Polar Research, 2017)
Dronning Maud Land (DML) in East Antarctica is considered to be a key area for the reconstruction of the Gondwana supercontinent. We investigate the crustal shear wave velocity (Vs) model beneath the Maitri station, situated in the central DML of East Antarctica, through receiver function modelling. The analysis shows an average crustal thickness of 38.50 ± 0.5 km and a Vp/Vs ratio of 1.784 ± 0.002. The obtained Vs structure suggests that the topmost ca. 2.5 km of the crust contains ice and sediments with low Vs (1.5–2.0 km/s). This layer is underlain by a thick (ca. 12.5 km) layer of Vs = 2.25–2.6 km/s, suggestive of an extrusive igneous rock (rhyolite) at this depth range. Between 16 and 28 km depth, the Vs increases from 2.9 to 3.4 km/s. In the lower crust, a 7 km thick layer of Vs = 3.9 km/s is followed by 6 km thick underplated layer (Vs = 4.1 km/s) at the crust–mantle boundary. The uppermost mantle Vs is ca. 4.3 km/s. With the observation of underplated material in the lowermost crust, extrusive volcanic rocks in the upper crust, seaward dipping reflectors in the surrounding and a general paucity of seismicity, we believe the crust beneath the Maitri station represents a volcanic passive continental margin. We also believe that after its origin in the Precambrian and during its subsequent evolution it might have been affected by the post-Precambrian tectono-thermal event(s) responsible for the Gondwana supercontinent break-up.
Keywords: Dronning Maud Land; geofysikk; kontinentalmargin; seismologi; tektonikk; vulkaner

Occurrence and average behavior of pulsating aurora - Partamies, Noora; Whiter, Daniel; Kadokura, Akira; Kauristie, Kirsti; Nesse Tyssøy, Hilde; Massetti, Stefano; Stauning, Peter; Raita, Tero (Journal of Geophysical Research: Space Physics, 2017)
Motivated by recent event studies and modeling efforts on pulsating aurora, which conclude that the precipitation energy during these events is high enough to cause significant chemical changes in the mesosphere, this study looks for the bulk behavior of auroral pulsations. Based on about 400 pulsating aurora events, we outline the typical duration, geomagnetic conditions, and change in the peak emission height for the events. We show that the auroral peak emission height for both green and blue emission decreases by about 8 km at the start of the pulsating aurora interval. This brings the hardest 10% of the electrons down to about 90 km altitude. The median duration of pulsating aurora is about 1.4 h. This value is a conservative estimate since in many cases the end of event is limited by the end of auroral imaging for the night or the aurora drifting out of the camera field of view. The longest durations of auroral pulsations are observed during events which start within the substorm recovery phases. As a result, the geomagnetic indices are not able to describe pulsating aurora. Simultaneous Antarctic auroral images were found for 10 pulsating aurora events. In eight cases auroral pulsations were seen in the southern hemispheric data as well, suggesting an equatorial precipitation source and a frequent interhemispheric occurrence. The long lifetimes of pulsating aurora, their interhemispheric occurrence, and the relatively high-precipitation energies make this type of aurora an effective energy deposition process which is easy to identify from the ground-based image data.
Keywords: Antarktis; astronomi; atmosfæren; geofysikk; geomagnetiske stormer; mesosfæren; meteorologi; polarlys

Observations of energetic turbulence on the Weddell Sea continental slope - Fer, Ilker; Darelius, Elin; Daae, Kjersti B (Geophysical Research Letters, 2016)
Turbulence profile measurements made on the upper continental slope and shelf of the southeastern Weddell Sea reveal striking contrasts in dissipation and mixing rates between the two sites. The mean profiles of dissipation rates from the upper slope are 1–2 orders of magnitude greater than the profiles collected over the shelf in the entire water column. The difference increases toward the bottom where the dissipation rate of turbulent kinetic energy and the vertical eddy diffusivity on the slope exceed 10−7 W kg−1 and 10−2 m2 s−1, respectively. Elevated levels of turbulence on the slope are concentrated within a 100 m thick bottom layer, which is absent on the shelf. The upper slope is characterized by near-critical slopes and is in close proximity to the critical latitude for semidiurnal internal tides. Our observations suggest that the upper continental slope of the southern Weddell Sea is a generation site of semidiurnal internal tide, which is trapped along the slope along the critical latitude, and dissipates its energy in a 100 m thick layer near the bottom and within 10 km across the slope.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; havstrømmer; hydrografi; kontinentalsokkel

Tilt signals at Mount Melbourne, Antarctica: evidence of a shallow volcanic source - Gambino, Salvatore; Aloisi, Marco; Falzone, Giuseppe; Ferro, Angelo (Polar Research, 2016)
Mount Melbourne (74°21′ S, 164°43′ E) is a quiescent volcano located in northern Victoria Land, Antarctica. Tilt signals have been recorded on Mount Melbourne since early 1989 by a permanent shallow borehole tiltmeter network comprising five stations. An overall picture of tilt, air and permafrost temperatures over 15 years of continuous recording data is reported. We focused our observations on long-term tilt trends that at the end of 1997 showed coherent changes at the three highest altitude stations, suggesting the presence of a ground deformation source whose effects are restricted to the summit area of Mount Melbourne. We inverted these data using a finite spherical body source, thereby obtaining a shallow deflation volume source located under the summit area. The ground deformation observed corroborates the hypothesis that the volcanic edifice of Mount Melbourne is active and should be monitored multidisciplinarily.Keywords: Tilt monitoring; volcanic dynamics; physics volcanology; ground deformation; Victoria Land.
Keywords: Antarktis; geofysikk; tektonikk; vulkaner

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

Magnetotelluric investigation of the Vestfold Hills and Rauer Group, East Antarctica - Peacock, Jared; Selway, Kate (Journal of Geophysical Research: Solid Earth, 2016)
The Vestfold Hills and Rauer Group in East Antarctica have contrasting Archean to Neoproterozoic geological histories and are believed to be juxtaposed along a suture zone that now lies beneath the Sørsdal Glacier. Exact location and age of this suture zone are unknown, as is its relationship to regional deformation associated with the amalgamation of East Gondwana. To image the suture zone, magnetotelluric (MT) data were collected in Prydz Bay, East Antarctica, mainly along a profile crossing the Sørsdal Glacier and regions inland of the Vestfold Hills and Rauer Group islands. Time-frequency analysis of the MT time series yielded three important observations: (1) Wind speeds in excess of ∼8 m/s reduce coherence between electric and magnetic fields due to charged wind-blown particles of ice and snow. (2) Estimation of the MT transfer function is best between 1000 and 1400 UT when ionospheric Hall currents enhance the magnetic source field. (3) Nonplanar source field effects were minimal but detectable and removed from estimation of the MT transfer function. Inversions of MT data in 2-D and 3-D produce similar resistivity models, where structures in the preferred 3-D resistivity model correlate strongly with regional magnetic data. The electrically conductive Rauer Group is separated from the less conductive Vestfold Hills by a resistive zone under the Sørsdal Glacier, which is interpreted to be caused by oxidation during suturing. Though a suture zone has been imaged, no time constrains on suturing can be made from the MT data.
Keywords: Antarktis; geofysikk; geologi; magnetotelluriske målinger

The impact of energetic electron precipitation on mesospheric hydroxyl during a year of solar minimum - Zawedde, Annet Eva; Nesse Tyssøy, Hilde; Hibbins, Robert; Espy, Patrick J; Ødegaard, Linn-Kristine Glesnes; Sandanger, Marit Irene; Stadsnes, Johan (Journal of Geophysical Research: Space Physics, 2016)
In 2008 a sequence of geomagnetic storms occurred triggered by high-speed solar wind streams from coronal holes. Improved estimates of precipitating fluxes of energetic electrons are derived from measurements on board the NOAA/POES 18 satellite using a new analysis technique. These fluxes are used to quantify the direct impact of energetic electron precipitation (EEP) during solar minimum on middle atmospheric hydroxyl (OH) measured from the Aura satellite. During winter, localized longitudinal density enhancements in the OH are observed over northern Russia and North America at corrected geomagnetic latitudes poleward of 55°. Although the northern Russia OH enhancement is closely associated with increased EEP at these longitudes, the strength and location of the North America enhancement appear to be unrelated to EEP. This OH density enhancement is likely due to vertical motion induced by atmospheric wave dynamics that transports air rich in atomic oxygen and atomic hydrogen downward into the middle atmosphere, where it plays a role in the formation of OH. In the Southern Hemisphere, localized enhancements of the OH density over West Antarctica can be explained by a combination of enhanced EEP due to the local minimum in Earth's magnetic field strength and atmospheric dynamics. Our findings suggest that even during solar minimum, there is substantial EEP-driven OH production. However, to quantify this effect, a detailed knowledge of where and when the precipitation occurs is required in the context of the background atmospheric dynamics.
Keywords: Antarktis; astronomi; energiske partikler; geofysikk; geomagnetiske stormer; planetbølger; solvind

Advancements in decadal climate predictability: The role of nonoceanic drivers - Bellucci, Alessio; Haarsma, Rein; Bellouin, Nicolas; Booth, Ben B; Cagnazzo, Chiara; van den Hurk, Bart; Keenlyside, Noel; Koenigk, Torben; Massonnet, François; Materia, Stefano; Weiss, M (Reviews of Geophysics, 2015)
We review recent progress in understanding the role of sea ice, land surface, stratosphere, and aerosols in decadal-scale predictability and discuss the perspectives for improving the predictive capabilities of current Earth system models (ESMs). These constituents have received relatively little attention because their contribution to the slow climatic manifold is controversial in comparison to that of the large heat capacity of the oceans. Furthermore, their initialization as well as their representation in state-of-the-art climate models remains a challenge. Numerous extraoceanic processes that could be active over the decadal range are proposed. Potential predictability associated with the aforementioned, poorly represented, and scarcely observed constituents of the climate system has been primarily inspected through numerical simulations performed under idealized experimental settings. The impact, however, on practical decadal predictions, conducted with realistically initialized full-fledged climate models, is still largely unexploited. Enhancing initial-value predictability through an improved model initialization appears to be a viable option for land surface, sea ice, and, marginally, the stratosphere. Similarly, capturing future aerosol emission storylines might lead to an improved representation of both global and regional short-term climatic changes. In addition to these factors, a key role on the overall predictive ability of ESMs is expected to be played by an accurate representation of processes associated with specific components of the climate system. These act as “signal carriers,” transferring across the climatic phase space the information associated with the initial state and boundary forcings, and dynamically bridging different (otherwise unconnected) subsystems. Through this mechanism, Earth system components trigger low-frequency variability modes, thus extending the predictability beyond the seasonal scale.
Keywords: Sørishavet; geofysikk; havis; klimaendringer; klimamodeller; meteorologi; polarområdene; sjøis

The WEGAS / GEA IV Geophysical Survey in eastern and southern Dronning Maud Land - Eagles, Graeme; Ruppel, Antonia; Steinhage, Daniel; Jokat, Wilfried; Läufer, Andreas; Jacobs, Joachim ([German Society for Polar Research], 2015)
The Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) and the Federal Institute for Geosciences and Natural Resources (BGR) collected around 150 hours of new gravity, magnetic and ice-penetrating radar data from east and south of Princess Elisabeth station in Dronning Maud Land between 2013 and 2015. Survey lines were spaced 10 km apart. The 2013/2014 and 2014/2015 used different gravimeters; a LaCoste and Romberg AirSea gravimeter (LCR) at constant barometric altitude and a Gravimetric Technologies GT2A gravimeter at constant ground separation. Both surveys used a Scintrex Cs-3 caesium vapour magnetometer mounted in a tail boom with compensation for the airframe calculated using a fuselage-mounted three-component fluxgate magnetometer. The GT2A gravity data reflect the effects of short-wavelength density contrasts between basement rocks and the ice sheet more reliably than the LCR data. Cross-over analysis suggests the repeatability of data collection with the GT2A lies at the sub-milliGal level. A broad subglacial channel that separates eastern Sør Rondane from the Yamato Belgica Mountains is evident in the gravity data. In the south of the survey region, the data reveal a dendritic pattern of subglacial valleys that converge towards the SW. Strong NS-trending magnetic anomalies coincide with the Yamato-Belgica Mountains. Further west, subtler ESE-trending anomalies confirm proposals that the SE Dronning Maud Land province continues into the region south of eastern Sør Rondane. An unexpected feature of both data sets is the apparent termination of the anomaly patterns associated with the province at a NNW-trending anomaly running south of Princess Elisabeth.
Keywords: Dronning Maud Land; geofysikk; geovitenskap

East Antarctica and supercontinent configuration: the Dronning Maud Land perspective - Jacobs, Joachim; Elburg, Marlina; Läufer, Andreas; Jokat, Wilfried (Japan Geoscience Union, 2015)
The geology of East Antarctica and its correlation in major supercontinents is highly speculative, since only a very small part of it is exposed. Therefore a better connection between geology and geophysics is needed in order to correlate exposed regions with ice-covered, geophysically-defined, blocks. In Dronning Maud Land (DML), two distinct late Mesoproterozoic/early Neoproterozoic tectono-metamorphic provinces appear, separated by the major, NE-trending Forster Magnetic Anomaly and South Orvin Shear Zone. To the west of this lineament, the Maud Belt has clear affinities with Grenville-age continent-continent mobile belts. East of the Forster Magnetic Anomaly, juvenile rocks with early Neoproterozoic age (Rayner-age) and an accretionary character crop out. The international GEA-II expedition (2012) targeted a white spot on the geological map immediately to the E of the Forster Magnetic Anomaly. This area allows the characterization and ground-truthing of a large and mostly ice-covered region, the SE DML Province that had previously been interpreted as an older cratonic block. However, new SHRIMP/SIMS zircon analyses and their geochemistry indicates that the exposed basement consists of a ca. 1000-900 Ma juvenile terrane that is very similar to rocks in Sor Rondane. It lacks significant metamorphic overprint at the end of crust formation, but it shows medium to high-grade overprinting between ca. 630-520 Ma, associated with significant felsic melt production, including A-type granitoid magmatism. Therefore, the aeromagnetically distinct SE DML province does neither represent the foreland of a Late Neoproterozoic/EarlyPaleozoic mobile belt, nor a craton, as has previously been speculated. It more likely represents the more juvenile, westward continuation of Rayner-age crust (1000-900 Ma). To the west it abuts along the NE-trending Forster Magnetic Anomaly. The latter is interpreted as a suture, which separates typical Grenville-age crust of the Maud Belt (ca. 1200-1030 Ma) to the W from Rayner-age crust to the E. Therefore the larger eastern part of DML has clearly Indian affinities. Its juvenile character with a lack of metamorphic overprint at the end of crust formation points to an accretionary history along this part of the Indian segment of Rodinia, immediately following final Rodinia assembly.
Keywords: Dronning Maud Land; geofysikk; geologi

The potential response of the hydrate reservoir in the South Shetland Margin, Antarctic Peninsula, to ocean warming over the 21st century - Marín-Moreno, Hector; Giustiniani, Michela; Tinivella, Umberta (Polar Research, 2015)
In the South Shetland Margin (SSM), Antarctic Peninsula, a bottom-simulating reflector indicates the presence of hydrate between ca. 500 and 3000 m water depth (mwd). The cold seabed temperatures allow hydrate stability at shallower water depths. During the past five decades, the Antarctic Peninsula has been warming up faster than any other part of the Southern Hemisphere, and long-term ocean warming could affect the stability of the SSM hydrate reservoir at shallow waters. Here, we model the transient response of the SSM hydrate reservoir between 375 and 450 mwd to ocean warming for the period 1958–2100. For the period 1958–2010, seabed temperatures are given by oceanographic measurements in the area, and for 2010–2100 by two temperature scenarios represented by the observed trends for the periods 1960–2010 (0.0034°C y−1) and 1980–2010 (0.023°C y−1). Our results show no hydrate-sourced methane emissions for an ocean warming rate at the seabed of 0.0034 °C y−1. For a rate of 0.023°C y−1, emissions start in 2028 at 375 mwd and extend to 442 mwd at an average rate of about 0.91 mwd y−1, releasing ca. 1.13×103 mol y−1 of methane per metre along the margin by 2100. These emissions originate from dissociation at the top of the hydrate layer, a physical process that steady-state modelling cannot represent. Our results are speculative on account of the lack of direct evidence of a shallow water hydrate reservoir, but they illustrate that the SSM is a key area to observe the effects of ocean warming-induced hydrate dissociation in the coming decades. Keywords: Hydrate; ocean warming; methane emissions; transient modelling; South Shetland Margin; Antarctic Peninsula.
Keywords: Sørishavet; geofysikk; havbunnen; havoppvarming; metanutslipp; oseanografi

Ozone-induced climate change propped up by the Southern Hemisphere oceanic front - Ogawa, Fumiaki; Omrani, Nour-Eddine; Nishii, Kazuaki; Nakamura, Hisashi; Keenlyside, Noel (Geophysical Research Letters, 2015)
The late twentieth century was marked by a significant summertime trend in the Southern Annular Mode (SAM), the dominant mode of tropospheric variability in the extratropical Southern Hemisphere (SH). This trend with poleward shifting tropospheric westerlies was attributed to downward propagation of stratospheric changes induced by ozone depletion. However, the role of the ocean in setting the SAM response to ozone depletion and its dynamical forcing remains unclear. Here we show, using idealized experiments with a state-of-the-art atmospheric model and analysis of Intergovernmental Panel on Climate Change climate simulations, that frontal sea surface temperature gradients in the midlatitude SH are critical for translating the ozone-induced stratospheric changes down to the surface. This happens through excitation of wave forcing, which controls the vertical connection of the tropospheric SAM with the stratosphere and shows the importance of internal tropospheric dynamics for stratosphere/troposphere coupling. Thus, improved simulation of oceanic fronts may reduce uncertainties in simulating SH ozone-induced climate changes.
Keywords: Sørishavet; geofysikk; havet; havstrømmer; klimaendringer; ozonhull; ozonlaget

Investigating the recent apparent hiatus in surface temperature increases: 2. Comparison of model ensembles to observational estimates - Thorne, Peter; Outten, Stephen; Bethke, Ingo; Seland, Øyvind (Journal of Geophysical Research: Atmospheres, 2015)
To assess published hypotheses surrounding the recent slowdown in surface warming (hiatus), we compare five available global observational surface temperature estimates to two 30-member ensembles from the Norwegian Earth System Model (NorESM). Model ensembles are initialized in 1980 from the transient historical runs and driven with forcings used in the CMIP5 experiments and updated forcings based upon current observational understanding, described in Part 1. The ensembles' surface temperature trends are statistically indistinguishable over 1998–2012 despite differences in the prescribed forcings. There is thus no evidence that forcing errors play a significant role in explaining the hiatus according to NorESM. The observations fall either toward the lower portion of the ensembles or, for some observational estimates and regions, outside. The exception is the Arctic where the observations fall toward the upper ensemble bounds. Observational data set choices can make a large difference to findings of consistency or otherwise. Those NorESM ensemble members that exhibit Nino3.4 Sea Surface Temperature (SST) trends similar to observed also exhibit comparable tropical and to some extent global mean trends, supporting a role for El Nino Southern Oscillation in explaining the hiatus. Several ensemble members capture the marked seasonality observed in Northern Hemisphere midlatitude trends, with cooling in the wintertime and warming in the remaining seasons. Overall, we find that we cannot falsify NorESM as being capable of explaining the observed hiatus behavior. Importantly, this is not equivalent to concluding NorESM could simultaneously capture all important facets of the hiatus. Similar experiments with further, distinct, Earth System Models are required to verify our findings.
Keywords: Antarktis; atmosfæren; fjernmåling; geofysikk; klimaendringer; klimatologi; meteorologi; observasjoner; polarområdene; temperatur

Late Holocene climate change recorded in proxy records from a Bransfield Basin sediment core, Antarctic Peninsula - Barnard, Alex; Wellner, Julia S; Anderson, John B (Polar Research, 2014)
The glacimarine environment of the Antarctic Peninsula region is one of the fastest warming places on Earth today, but details of changes in the recent past remain unknown. Large distances and widespread variability separate late Holocene palaeoclimate reconstructions in this region. This study focuses on a marine sediment core collected from ca. 2000 m below sea level in the Central Bransfield Strait that serves as a key for understanding changes in this region. The core yielded a high sedimentation rate and therefore provides an exceptional high-resolution sedimentary record composed of hemipelagic sediment, with some turbidites. An age model has been created using radiocarbon dates that span the Late Holocene: 3560 cal yr BP to present. This chronostratigraphic framework was used to establish five units, which are grouped into two super-units: a lower super-unit (3560–1600 cal yr BP) and an upper super-unit (1600 cal yr BP–present), based on facies descriptions, laser particle size analysis, x-ray analysis, multi-sensor core logger data, weight percentages and isotopic values of total organic carbon and nitrogen. We interpret the signal contained within the upper super-unit as an increase in surface water irradiance and/or shortening of the sea-ice season and the five units are broadly synchronous with climatic intervals across the Antarctic Peninsula region. While the general trends of regional climatic periods are represented in the Bransfield Basin core we have examined, each additional record that is obtained adds variability to the known history of the Antarctic Peninsula, rather than clarifying specific trends. Keywords: Antarctic Peninsula; palaeoclimate; Holocene; marine; isotopes.
Keywords: Antarktis; geofysikk; geokjemi; paleoklimatologi; sedimentologi

Reassembling Gondwana: A new high quality constraint from vibroseis exploration of the sub-ice shelf geology of the East Antarctic continental margin - Kristoffersen, Yngve; Hofstede, Coen; Diez, Anja; Blenkner, Richard; Lambrecht, Astrid; Mayer, Christoph; Eisen, Olaf (Journal of Geophysical Research: Solid Earth, 2014)
The breakup of Gondwana is manifested by coeval early Jurassic Karoo magmatism in South Africa and East Antarctica. In South Africa, the large volumes of volcanic rocks of the adjoining Lebombo and Mwenetzi-Save monoclines represent a volcanic rift margin, and in East Antarctica, a corresponding feature, the Explora Wedge is buried below sediments and floating ice shelves on the continental margin of Dronning Maud Land. We use the seismic vibrator source to explore the sub-ice geology in Antarctica, and the new seismic reflection and available regional aeromagnetic data enable us to outline a dogleg landward extent of the Explora Wedge in Dronning Maud Land. The congruent inboard wedge geometries on the two continents define a high quality constraint, which facilitate for the first time, a geologically consistent and tight reconstruction of Africa relative to East Antarctica within Gondwana. The uncertainties in correlations of major geological features (mobile belts) from one continent to the other may now be of the order of ten's of kilometers rather than hundreds of kilometers.
Keywords: Antarktis; geofysikk; geologi; kontinentalmargin; seismologi; stratigrafi

Low melt rates with seasonal variability at the base of Fimbul Ice Shelf, East Antarctica, revealed by in situ interferometric radar measurements - Langley, Kirsty; Kohler, Jack; Sinisalo, Anna; Øyan, Mats Jørgen; Hamran, Svein Erik; Hattermann, Tore; Matsuoka, Kenichi; Nøst, Ole Anders; Isaksson, Elisabeth (Geophysical Research Letters, 2014)
Basal melt is a major cause of ice shelf thinning affecting the stability of the ice shelf and reducing its buttressing effect on the inland ice. The Fimbul ice shelf (FIS) in Dronning Maud Land (DML), East Antarctica, is fed by the fast-flowing Jutulstraumen glacier, responsible for 10% of ice discharge from the DML sector of the ice sheet. Current estimates of the basal melt rates of the FIS come from regional ocean models, autosub measurements, and satellite observations, which vary considerably. This discrepancy hampers evaluation of the stability of the Jutulstraumen catchment. Here, we present estimates of basal melt rates of the FIS using ground-based interferometric radar. We find a low average basal melt rate on the order of 1 m/yr, with the highest rates located at the ice shelf front, which extends beyond the continental shelf break. Furthermore, our results provide evidence for a significant seasonal variability.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbre; isshelf; kontinentalsokkel; smelting

Basal mass budget of Ross and Filchner-Ronne ice shelves, Antarctica, derived from Lagrangian analysis of ICESat altimetry - Moholdt, Geir; Padman, Laurie; Fricker, Helen Amanda (Journal of Geophysical Research: Earth Surface, 2014)
Traditional methods of deriving temporal variability of Antarctic ice-shelf elevation from satellite altimetry use a fixed (“Eulerian”) reference frame, where the measured changes include advection of ice thickness gradients between measurement epochs. We present a new method which removes advection effects by using an independent velocity field to compare elevations in a moving (“Lagrangian”) reference frame. Applying the technique to ICESat laser altimetry for the period 2003–2009 over the two largest Antarctic ice shelves, Ross and Filchner-Ronne, we show that the Lagrangian approach reduces the variability of derived elevation changes by about 50% compared to the Eulerian approach and reveals clearer spatial patterns of elevation change. The method simplifies the process of estimating basal mass budget from the residual of all other processes that contribute to ice-shelf elevation changes. We use field data and ICESat measurements over ice rises and the grounded ice sheet to account for surface accumulation and changes in firn air content, and remove the effect of ice-flow divergence using surface velocity and ice thickness data. The results show highest basal melt rates (>5 m a−1) near the deep grounding lines of major ice streams, but smaller melt rates (<5 m a−1) near the ice-shelf fronts are equally important to total meltwater production since they occur over larger areas. Integrating over the entire ice-shelf areas, we obtain basal mass budgets of −50 ± 64 Gt a−1 for Ross and −124 ± 66 Gt a−1 for Filchner-Ronne, with changes in firn air content as the largest error source.
Keywords: Sørishavet; batymetri; brehylle; geofysikk; innlandsis; isbrem; isshelf; oseanografi; satellite altimetri

Å filme de dypfrosne hemmelighetene til en aktiv vulkan - Roberts, Jason (Polarboken, 2014)
Keywords: Antarktis; film; geofysikk; vulkaner

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

The influence of Nunataks on atmospheric boundary layer convection during summer in Dronning Maud Land, Antarctica - Stenmark, Aurora; Hole, Lars Robert; Voss, Paul; Reuder, Joachim; Jonassen, Marius O (Journal of Geophysical Research: Atmospheres, 2014)
The effects of nunataks on temperature profiles and wind patterns are studied using simulations from the Weather Research and Forecasting model. Simulations are compared to hourly observations from an automatic weather station located at the Troll Research Station in Dronning Maud Land. Areas of bare ground have been implemented in the model, and the simulations correspond well with meteorological measurements acquired during the 4 day simulation period. The nunataks are radiatively heated during daytime, and free convection occurs in the overlying atmospheric boundary layer. The inflow below the updraft forces strong horizontal convergence at the surface, whereas weaker divergence appears aloft. In a control run with a completely ice-covered surface, the convection is absent. In situ observations carried out by a remotely controlled balloon and a small model airplane compare well with model temperature profiles, but these are only available over the ice field upwind to the nunatak.
Keywords: Dronning Maud Land; atmosfæren; geofysikk; meteorologi; nunataker; observasjoner

Neoproterozoic/Lower Palaeozoic geodynamic evolution of Dronning Maud Land: integrating geology and geophysics - Jacobs, Joachim; Läufer, Andreas; Clark, Chris; Kleinhanns, Ilka; Elburg, Marlina; Ruppel, Antonia; Estrada, Solveig; Damaske, Detlef; Jokat, Wilfried; Riedel, Sven; Lucka, Nicole (Changing polar regions : 25th International Congress on Polar Research ; March 17-22, 2013, Hamburg, Germany, 2013)
East Antarctica probably formed by amalgamation of a number of cratons along distinct Ediacaran mobile belts, including the ca. 600-500 Ma East African-Antarctic Orogen (EAAO) that dissects Dronning Maud Land (DML). New field-work during the international expeditions Geodynamic Evolution of East Antarctica (GEA) I + II in the austral summers 2010/11 and 2011/12, and first geochronological results from eastern DML reveal a complex tectonic architecture across the belt. In western DML, the EAAO reworks older Mesoproterozoic crust of the Maud Belt; the westernmost boundary of the mobile belt is characterized by a major dextral transpressional shear zone. In central DML, a major magnetic anomaly, the Forster anomaly, was interpreted as a cryptic suture of the EAAO (Riedel et al. 2012). The area where the Forster anomaly crosses the DML mountains is poorly investigated so far, but appears to coincide with a major strike slip shear zone in the southern Kurze Mts. and the occurrence of major Ediacaran granulite bodies. East of the Forster anomaly, the magnetic anomaly pattern changes significantly and typical Maud type crust is not present any longer. GEA II targeted a range of nunataks between Sør Rondane and central DML that had never been visited previously (from Blåklettane and Bergekongen in the E to Urna and Sørsteinen in the W). These nunataks are dominated by medium- to high-grade metasedimentary and metavolcanic rocks of possibly Neoproterozoic age, including abundant marble and graphite schists. Sør Rondane in eastern DML, is dominated by two distinct blocks separated by the dextral Main Shear Zone. The northwestern block is still part of the eastern EAAO, where new SHRIMP zircon data from metamorphic rims provide ages of ca. 560 Ma. The southeastern block is made up of a TTG terrane, which provides four new SHRIMP zircon dates between 990-980 Ma, interpreted as igneous crystallization ages (oceanic arc). The TTG terrane shows limited tectonic overprint and is likely the southeastern foreland of the EAAO. Close to the contact of the two blocks grey geisses and augen-gneisses gave zircon crystallization ages of ca. 750 Ma, ages which were previously unknown from the EAAO. The Forster anomaly therefore separates distinctly different parts of the EAAO: a) a reworked, mainly Grenville-age crust to the W (the overprinted margin of the Kalahari Craton) and b) a part of the orogen dominated by Neoproterozoic accretionary tectonics to the E. This difference is also reflected in the geochemistry of voluminous late-tectonics granitoids across the belt.
Keywords: Dronning Maud Land; geofysikk; geologi

Low frequency variability on the continental slope of the southern Weddell Sea - Jensen, Mari F; Fer, Ilker; Darelius, Elin (Journal of Geophysical Research: Oceans, 2013)
One-year long records of temperature, salinity, and currents show seasonally varying, energetic oscillations with a dominant period of approximately 35 h on the upper continental slope of the southern Weddell Sea. The data set is sampled by five moorings deployed on the slope of the Crary Fan, east of the main outflow site of the Filchner overflow plume. The characteristics of the observed oscillations are compared to idealized coastal trapped waves inferred from a numerical code. The variability at 35 h period is identified as mode 1 waves with wavelengths less than 200 km and group velocity opposing the phase speed, indicating energy propagation toward east. Filchner Depression and the nearby ridges on the slope are suggested as the generation site where the dynamics associated with the overflow plume can force the variability. Historical time series at the overflow site are revisited to identify the source of previously reported variability at 3 and 6 day time scales. Mode 2 waves at wavelengths of about 100 and 1000 km were found to bear resemblance to the 3 day and 6 day variability, respectively. The seasonal variation in the energy in the 35 h band shows small but significant correlation with the low frequency easterly winds. The presence of coastal trapped waves along the continental slope of the Weddell Sea can increase the heat exchange across the shelf break and affect the dense water production rates.
Keywords: Sørishavet; Weddellhavet; batymetri; bunnvann; geofysikk; havstrømmer; kelvinbølger; saltinnhold; temperatur måling

Electrical structure beneath Schirmacher Oasis, East Antarctica: a magnetotelluric study - Murthy, D N; Veeraswamy, K; Harinarayana, T; Singh, U K; Santosh, M (Polar Research, 2013)
Maitri Station (70.76°S; 11.73°E) is located in Schirmacher Oasis, a coastal nunatak in north-central Dronning Maud Land covering an area of 35 km2. Here, we report results from the first magnetotelluric experiments and delineate the deep electrical conductivity structure under Schirmacher Oasis using the data acquired during the 24th Indian Antarctic Scientific Expedition. The magnetotelluric method has the advantage of shallow to deeper level coverage as the data acquisition covers a wide frequency band of 10-3103 Hz, permitting different penetration depths depending on the frequency and conductivity of the layer under investigation. The modelling results indicate the presence of a highly resistive (8000-10 000 ohm m) upper crust, which shows a lateral variation in thickness from 20 km (below site 6) in the east to 10 km (between sites 1 and 2) in the west. It is underlain by a less resistive (500-600 ohm m) lower crust. The highly resistive upper crustal structure supports the existing notion that western Dronning Maud Land is a stable, cratonic platform. Results of free-air gravity, seismic, geomagnetic and surface wave dispersion investigations in East Antarctica also indicate a cratonic-type crust. The results of our study allow us to identify a westward thinning of the upper crust with a marked boundary between sites 1 and 2. We also find evidence for the continuity of the Mozambique mobile belt in East Antarctica on the western side of Schirmacher Oasis. Keywords: Magnetotellurics; Schirmacher Oasis crustal structure; East Antarctica; Mozambique Belt; electrical conductivity.
Keywords: Dronning Maud Land; geofysikk; geologi; magnetotelluriske eksperimenter

The effect of energetic electron precipitation on middle mesospheric night-time ozone during and after a moderate geomagnetic storm - Daae, Marianne; Espy, Patrick J; Nesse Tyssøy, Hilde; Newnham, David A; Stadsnes, Johan; Søraas, Finn (Geophysical Research Letters, 2012)
Using a ground-based microwave radiometer at Troll Station, Antarctica (72°S, 2.5°E,L = 4.76), we have observed a decrease of 20–70% in the mesospheric ozone, coincident with increased nitric oxide, between 60 km and 75 km altitude associated with energetic electron precipitation (E > 30 keV) during a moderate geomagnetic storm (minimum Dst of −79 nT) in late July 2009. NOAA satellite data were used to identify the precipitating particles and to characterize their energy, spatial distribution and temporal variation over Antarctica during this isolated storm. Both the ozone decrease and nitric oxide increase initiate with the onset of the storm, and persist for several days after the precipitation ends, descending in the downward flow of the polar vortex. These combined data present a unique case study of the temporal and spatial morphology of chemical changes induced by electron precipitation during moderate geomagnetic storms, indicating that these commonplace events can cause significant effects on the middle mesospheric ozone distribution.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; mikrobølge; ozonlaget; radiometer

Spatial variation of englacial radar attenuation: Modeling approach and application to the Vostok flowline - MacGregor, Joseph A.; Matsuoka, Kenichi; Waddington, Edwin D.; Winebrenner, Dale P.; Pattyn, Frank (Journal of Geophysical Research: Earth Surface, 2012)
Constraining the spatial variation of englacial radar attenuation is critical for accurate inference of the spatial variation of the englacial and basal properties of ice sheets from radar returned power. Here we evaluate attenuation models that account for spatial variations in ice temperature and chemistry and test them along the flowline that passes through the Vostok ice core site, Antarctica. The simplest model, often used but rarely valid, assumes a uniform attenuation rate everywhere along the flowline, so that total attenuation is proportional to ice thickness. The next simplest model uses spatially varying temperatures predicted by an ice-flow model and assumes uniform chemistry. Additional models account for spatially varying chemistry using englacial stratigraphy. We find that the roundtrip attenuation to the bed can easily differ by 10 dB or more between the uniform attenuation-rate model and models that account for variable ice temperature. Such differences are sufficient to confound the delineation of dry and wet beds. Also including spatial variations in chemistry produces smaller differences (<10 dB), but the magnitude of these differences depends on the relative importance of dry and wet deposition of impurities in the past. Accounting for dry-deposited impurities requires ice-flow modeling and results in larger differences from all other models, which assume uniform chemistry or wet deposition only. These results indicate that modeling the spatial variation of attenuation requires a spatially varying temperature model in order to infer bed conditions from bed returned power accurately, and that both ice core data and radar stratigraphy are also strongly desirable.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis

Recovery Lakes, East Antarctica: Radar assessment of sub-glacial water extent - Langley, Kirsty; Kohler, Jack; Matsuoka, Kenichi; Sinisalo, Anna; Scambos, Ted; Neumann, Thomas; Muto, Atsuhiro; Winther, Jan-Gunnar; Albert, Mary (Geophysical Research Letters, 2011)
A fast-flowing tributary of Recovery ice stream penetrates more than 500 km into the interior of East Antarctica. Recent satellite-based studies found surface features in the onset area of this tributary that indicate a significant subglacial hydraulic system, including four large smooth basins, the typical surface expression of large subglacial lakes, as well as eleven smaller areas over which ice-sheet surface elevations rapidly changed by discharge/filling of subglacial water. Here we present the first ice-penetrating radar evidence of subglacial conditions in this area. We identified a distinct ice-water interface only over a limited area within the boundaries of the investigated large smooth basins, previously hypothesized to be water-filled lakes. The radar characteristics in some areas are similar to those of a drained lake, indicating that parts of the bed are wet, but not a typical lake. We also find evidence for discrete water bodies outside of the lake boundaries. The lines of evidence indicate that the northern most two Recovery Lakes have recently drained.
Keywords: Antarktis; geofysikk; glasiologi; isbre; isstrøm; radar observasjoner; subglasial innsjø

Direct observations of nitric oxide produced by energetic electron precipitation into the Antarctic middle atmosphere - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Holmén, Kim; Horne, Richard B (Geophysical Research Letters, 2011)
We report the first ground-based passive microwave observations made from Troll station, Antarctica, which show enhanced mesospheric nitric oxide (NO) volume mixing ratio reaching levels of 1.2 ppmv, or 2–3 orders of magnitude above background, at 70–80 km during small, relatively isolated geomagnetic storms in 2008. The mesospheric NO peaked 2 days after enhanced NO at higher altitudes (110–150 km) measured by the SABER satellite, and 2 days after peaks in the >30 keV and >300 keV electron flux measured by POES, although the 300 keV electron flux remained high. High time resolution data shows that mesospheric NO was enhanced at night and decayed during the day and built up to high levels over a period of 3–4 days. The altitude profile of mesospheric NO suggests direct production by ∼300 keV electron precipitation. Simulations using the Sodankylä Ion and Neutral Chemistry model show that the delay between thermospheric and mesospheric NO enhancements was primarily a result of the weaker production rate at lower altitudes by ∼300 keV electrons competing against strong day-time losses.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; meteorologi; observasjoner; radiometer

Mesospheric wind semidiurnal tides within the Canadian Middle Atmosphere Model Data Assimilation System - Xu, Xiaoyong; Manson, Alan H; Meek, Christopher; Jacobi, Christoph; Hall, Chris; Drummond, James (Journal of Geophysical Research: Atmospheres, 2011)
The horizontal wind data from the standard version of Canadian Middle Atmosphere Model Data Assimilation System (CMAM-DAS) for the years 2006–2008 are analyzed to obtain the global structure and seasonal variability of the semidiurnal tide (SDT) in the mesosphere. The modeled amplitudes and phases of the SDTs at single stations from middle/high northern latitudes are quite similar to those observed by radars. The primary nonmigrating tides identified in both the meridional wind and zonal wind semidiurnal spectra at 88 km include the westward propagating wave numbers s = 1 (SW1), 3 (SW3), 4 (SW4), 6 (SW6), the standing s = 0 (S0), and the eastward propagating s = 2 (SE2). The migrating SDT (SW2) amplitude maxima usually occur at 40°N–60°N during December–February and August–September, and also at 40°S–60°S in April–May, with the dominance of (2, 4) during October–April and (2, 3) and (2, 5) dominance for other months. The CMAM-DAS is quite successful in reproducing the dominance of SW1 in the Antarctic summer mesosphere. The modeled SW1 shows very good overall agreement in both amplitude and phase with wind measurements from UARS High Resolution Doppler Imager and Wind Imaging Interferometer (UARS-HRDI/WINDII) and from TIMED Doppler Interferometer (TIDI). The CMAM-DAS analyses for SW3, SW4, SW6, and S0 are also in reasonable agreement with those determined from the HRDI/WINDII or TIDI wind measurements. This work provides further evidence for the tidal forcing from below.
Keywords: Antarktis; atmosfæren; atmosfærisk tidevann; geofysikk; meteorologi

A New Approach for Exploring Ice Sheets and Sub-Ice Geology - Eisen, Olaf; Hofstede, Coen; Miller, Heinrich; Kristoffersen, Yngve; Blenkner, Rick; Lambrecht, Astrid; Mayer, Christoph (Eos Transactions American Geophysical Union, 2010)
Keywords: Antarktis; geofysikk; geologi; innlandsis; seismologi

Wintertime mixed layer measurements at Maud Rise, Weddell Sea - Sirevaag, Anders; McPhee, Miles G; Morison, James H; Shaw, William J; Stanton, Timothy P (Journal of Geophysical Research: Oceans, 2010)
Sea ice plays a crucial role in the exchange of heat between the ocean and the atmosphere, and areas of intense air-sea-ice interaction are important sites for water mass modification. The Weddell Sea is one of these sites where a relatively thin first-year ice cover is constantly being changed by mixing of heat from below and stress exerted from the rapidly changing and intense winds. This study presents mixed layer turbulence measurements obtained during two wintertime drift stations in August 2005 in the eastern Weddell Sea, close to the Maud Rise seamount. Turbulence in the boundary layer is found to be controlled by the drifting ice. Directly measured heat fluxes compare well with previous studies and are well estimated from the mixed layer temperatures and mixing. Heat fluxes are also found to roughly balance the conductive heat flux in the ice; hence, little freezing/melting was observed. The under-ice topography is estimated to be hydraulically very smooth; comparison with a steady 1-D model shows that these estimates are made too close to the ice-ocean interface to be representative for the entire ice floe. The main source and sink of turbulent kinetic energy are shear production and dissipation. Observations indicate that the dynamics of the under-ice boundary layer are influenced by a horizontal variability in mixed layer density and an increasing amount of open leads in the area.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; havis; hydrografi; oseanografi; pyknoklin; sjøis

Seismic and radar investigations of Fourcade Glacier on King George Island, Antarctica - Young Kim, Ki; Lee, Joohan; Ho Hong, Myung; Kuk Hong, Jong; Keun Jin, Young; Shon, Howong (Polar Research, 2010)
To determine P- and S-wave velocities, elastic properties and subglacial topography of the polythermal Fourcade Glacier, surface seismic and radar surveys were conducted along a 470-m profile in November 2006. P- and S-wave velocity structures were determined by travel-time tomography and inversion of Rayleigh wave dispersion curves, respectively. The average P- and S-wave velocities of ice are 3466 and 1839 m s-1, respectively. Radar velocities were obtained by migration velocity analysis of 112 diffraction events. An estimate of 920 kg m-3 for the bulk density of wet ice corresponds to water contents of 5.1 and 3.2%, which were derived from the average P-wave and radar velocities, respectively. Using this density and the average P- and S-wave velocities, we estimate that the corresponding incompressibility and rigidity of the ice are 6.925 and 3.119 GPa, respectively. Synergistic interpretation of the radar profile and P- and S-wave velocities indicates the presence of a fracture zone above a subglacial high. Here, the P- and S-wave velocities are approximately 5 and 3% less than in the ice above a subglacial valley, respectively. The S-wave velocities indicate that warmer and less rigid ice underlies 10–15 m of colder ice near the surface of the glacier. Such layering is characteristic of polythermal glaciers. As a relatively simple non-invasive approach, integration of P-wave tomography, Rayleigh wave inversion and ground-towed radar is effective for various glaciological studies, including the elastic properties of englacial and subglacial materials, cold/warm ice interfaces, topography of a glacier bed and location of fracture zones.
Keywords: Antarktis; geofysikk; glasiologi; isbre; radarundersøkelse; seismisk undersøkelse; subglasial; tomografi; topografi

Isostatic stability of the East Antarctic station Dumont d’Urville from long-term geodetic observations and geophysical models - Amalvict, Martine; Willis, Pascal; Wöppelmann, Guy; Ivins, Erik R.; Bouin, Marie-Noëlle; Testut, Laurent; Hinderer, Jacques (Polar Research, 2009)
Geodetic measurements of the vertical crustal displacement collocated with absolute gravity changes provide a discriminatory measurement of present-day glacial changes, versus more deeply seated rock motions caused by glacial isostatic adjustment (GIA). At the East Antarctic station of Dumont d’Urville, we compare the displacements derived from continuous DORIS (1993.0– 2006.0) and Global Positioning System (GPS) (1999.0–2005.7) data, and observed changes in absolute gravity (2000–2006), with the predicted vertical displacement and change in gravity from GIA modelling. The geodetic results have mutual self-consistency, suggest station stability and provide upper bounds on both GIA and secular ice mass changes. The GIA models tend to predict amplitudes of rock motion larger than those observed, and we conclude that this part of Antarctica is probably experiencing a slight gain in ice mass, in contrast to West Antarctica.
Keywords: Antarktis; breendringer; geodesi; geofysikk; innlandsis; tidevannsmålinger

Revisiting sites of the South Pole Queen Maud Land Traverses in East Antarctica: Accumulation data from shallow firn cores - Anschütz, Helgard; Müller, Karsten; Isaksson, Elisabeth; McConnell, Joseph R.; Fischer, Helmut; Miller, Heinz; Albert, Mary; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2009)
[1] Ground-based accumulation measurements are scarce on the high East Antarctic plateau, but highly necessary for model validation and the interpretation of satellite data for the determination of Antarctic mass balance. Here, we present accumulation results obtained from four shallow firn cores drilled in the Antarctic summer season 2007/2008. The cores were drilled along the first leg of the Norwegian-US IPY traverse through East Antarctica, visiting sites like Plateau Station and Pole of Relative Inaccessibility that have been covered by the South Pole Queen Maud Land Traverses (SPQMLT) in the 1960s. Accumulation has been determined from volcanic chronology established from the conductivity records measured by dielectric profiling (DEP). The Tambora 1815/unknown 1809 double peak is clearly visible in the conductivity data and serves as a reliable time marker. Accumulation rates averaged over the period 1815–2007 are in the range of 16 to 32 kg m−2 a−1, somewhat lower than expected from the SPQMLT data. The spatial pattern is mainly influenced by elevation and continentality. Three of the firn cores show a decrease of more than 20% in accumulation for the time period 1815–2007 in relation to accumulation rates during the period 1641–1815. The spatial representativity of the firn cores is assessed by ground-penetrating radar, showing a rather smoothly layered pattern around the drill sites. Validation of the DEP results is utilized by comparison with chemistry data, proving the validity of the DEP method for dating firn cores. The results help understanding the status of the East Antarctic ice sheet and will be important for e.g. future model-derived estimates of the mass balance of Antarctica.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbreer; vulkaner

Mixing on the continental slope of the southern Weddell Sea - Daae, Kjersti L.; Fer, Ilker; Abrahamsen, E. Povl (Journal of Geophysical Research: Oceans, 2009)
Shipboard hydrography and current profiles collected in 2003 and time series from moored current meters deployed in late 1990s are analyzed to study the variability of mixing in the southeastern Weddell Sea. Profiles of eddy diffusivity Kρ are inferred from fine-scale shear (vertical derivative of horizontal velocity) and strain (vertical derivative of isopycnal displacement) variance using parameterizations which relate the internal wave energy to the dissipation rate at small scales. The highest mixing rates are seen near the bottom where the eddy diffusivities are elevated by 1 order of magnitude from those in the interior and exceed 10−4 m2 s−1. The observations show latitudinal variability in Kρ, particularly near the bottom, where Kρ significantly increases near 74° 28′S, the critical latitude for lunar semidiurnal (M2) tides. In this region, the critical latitude coincides with near-critical topography on the upper continental slope, a situation which favors generation of M2 internal waves. Consistent with the results from fine-scale shear and strain parameterizations, which indicate highest bottom diffusivities near the critical latitude, independent analysis of current time series from moored instruments shows a thickening of the frictional bottom boundary layer near the critical latitude. Semidiurnal tidal dynamics at the upper continental slope together with the critical latitude effects lead to mixing that might significantly affect the regional heat budget and the circulation in the study area.
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; hydrografi; kontinentalmargin; oseanografi; vannvirvler

Report from the Workshop on the Development of the Weddell Sea - Dronning Maud Land Regional Working Group SOOS - de Steur, Laura; Gutt, Julian; Moreau, Sebastien ([Zenodo], 2009)
This report summaries the first workshop of the Southern Ocean Observing System (SOOS) Weddell Sea and Dronning Maud Land (WS-DML) Regional Working Group held Tromsø, Norway, in January 2019.
Keywords: Dronning Maud Land; Sørishavet; geofysikk; geologi; konferanse; symposium

Tropical Pacific - high latitude south Atlantic teleconnections as seen in δ18O variability in Antarctic coastal ice cores - Divine, Dmitry; Isaksson, Elisabeth; Kaczmarska, Marzena; Godtliebsen, Fred; Oerter, Hans; Schlosser, Elisabeth; Johnsen, Sigfus J; van den Broeke, M; van de Wal, R S W (Journal of Geophysical Research: Atmospheres, 2009)
We use a network of eight ice cores from coastal Dronning Maud Land (DML), Antarctica, to examine the role of the tropical ENSO (El Niño-Southern Oscillation) in the temporal variability of δ18O in annual accumulation. The longest record from the S100 ice core covering the period 1737–1999 is used to analyze the teleconnections between the tropical Pacific and coastal DML on decadal scales and longer. A shorter stacked coastal DML δ18O series spanning 1955–1999 is constructed to assess the variability of ENSO teleconnection on interannual scales. Results suggest that, on typical ENSO timescales of 2–6 years, the strength of the teleconnection varies in time, being stronger for years with generally negative phase of the Southern Annular Mode (SAM). On the timescales of approximately two decades (bidecadal), positive isotope anomalies are associated with oceanic warming and a westward sea surface temperature (SST) gradient in the equatorial Pacific. Bidecadal variability in SAM, forced by the tropical Pacific, is proposed as a critical element in the teleconnection. Our analysis suggests that a multidecadal positive trend in the annual mean δ18O values from the analyzed cores can be indicative of the atmospheric warming that begun in this part of the DML already in the 1910s. The trend in δ18O, quantified in terms of long-term surface air temperature (SAT) changes, is consistent with the instrumental data. Yet, we speculate that the accurate estimation of SAT trends requires an assessment of the potential role of secular SAM and sea ice extent changes in shaping the isotopic signal.
Keywords: Dronning Maud Land; Sørishavet; geofysikk; klima

Fluid infiltration, heat transport, and healing of microcracks in the damage zone of magmatic veins: Numerical modeling - Engvik, Lars; Stöckhert, Bernhard; Engvik, Ane K (Journal of Geophysical Research: Solid Earth, 2009)
Alteration halos with sharp boundaries are flanking pegmatitic veins in high-grade metamorphic and magmatic rocks of Dronning Maud Land, Antarctica. These halos are interpreted to represent the damage zone, formed as the wake of the process zone at the tip of the propagating magma-filled fracture and infiltrated by the fluid phase liberated from the crystallizing hydrous melt. On the basis of a set of assumptions, our numerical model explores the time scales of the infiltration processes, taking into account the combined effects of fluid flow, heat transfer, and temperature-dependent decay of interconnected porosity due to microcrack healing. Assuming an initial magma temperature of 700°C, a far field temperature in the host rock of 300°C, an initial porosity range of 0.5–2% in the damage zone, a permeability of 10−16 m2, and a pressure difference of 300 MPa, we find that the fluid infiltration into the damage zone proceeds within seconds to minutes and that the fluid flow contributes significantly to the heat transfer into the host rock. Assuming an initial microcrack aperture of 1 μm, the model predicts that the crack healing time scale is significantly longer than that of fluid infiltration in the case of thin veins with narrow damage zones; in this case, crack healing does not hinder fluid infiltration. Only for thick veins with high heat content and prolonged crystallization history does permeability become reduced by crack healing during progressive fluid infiltration. The results indicate that the formation of the alteration halos flanking pegmatitic veins may be a quasi-instantaneous process on geological time scales.
Keywords: Dronning Maud Land; geofysikk; geologi; mineralogi

Den Norske Antarktis-ekspedisjonen, 1956-60: Norway Station - Henriksen, Hans Martin (Polarboken, 2008)
Keywords: Dronning Maud Land; ekspedisjoner; geofysikk; historie; logistikk

How representative is a time series derived from a firn core? A study at a low-accumulation site on the Antarctic plateau - Karlöf, Lars; Winebrenner, Dale P; Percival, Donald B (Journal of Geophysical Research: Earth Surface, 2006)
The acquisition and interpretation of increasingly high-resolution climate data from polar ice and firn cores motivates the question: What is the finest depth or timescale on which measurements on cores arrayed over a given area correlate? We analyze dated depth series of electrical and oxygen isotope measurements from a spatial array of firn cores with 3.5–7 km spacing in Dronning Maud Land, Antarctica, each with a temporal span of approximately 200 years. We use wavelet analysis to decompose the series into components associated with changes of averages on different scales, and thus deduce which scales are dominated by environmental noise, and which may contain a common signal. We find that common signals in electrical records have timescales of approximately 1–3 years. We identify only one electrical signal which rises significantly above the background in our 200-year records, evidently corresponding to the Tambora eruption. Several smaller signals correlate in a few of pairs of cores, one of which may correspond to a known volcanic event, but the others appear to be spurious. We present a simulation-based method for testing the significance of apparent electrical signal correlations, and highlight the importance of accurate relative dating between cores. In the case of oxygen-isotope records, we find, surprisingly, no significant correlation on any scale in the records, for any of the pairs of cores. There is, however, a weak trend toward positive correlation at longer timescales (up to 16 years). Statistical theory for the relevant confidence intervals and the observed statistics of the records permit estimation of the length of a data series necessary to reliably detect a hypothetical correlation equal to that observed. For the highest correlation observed on 16-year scales, core records of about 380 years (approximately 30 m at the Dronning Maud Land site) would be necessary to establish significance.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi; meteorologi; tidsserieanalyse

Modeling ocean processes below Fimbulisen, Antarctica - Smedsrud, Lars H.; Jenkins, Adrian; Holland, David M.; Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2006)
Model simulations of circulation and melting beneath Fimbulisen, Antarctica, obtained using an isopycnic coordinate ocean model, are presented. Model results compare well with available observations of currents and hydrography in the open ocean to the north of Fimbulisen and suggest that Warm Deep Water exists above the level of a sub-ice-shelf bedrock sill, the principal pathway for warm waters to enter the sub-ice-shelf cavity. The model shows a southward inflow of Warm Deep Water over this sill and into the cavity, producing a mean cavity temperature close to −1.0°C. This leads to high levels of basal melting (>10 m/a) at the grounding line of Jutulstraumen and an average melting over the ice shelf base close to 1.9 m/a. The southward inflow is a compensating flow caused by the northward outflow of fresh, cold water produced by the basal melting. Results on inflow and melting are difficult to validate since no in situ measurements yet exist in the cavity. If such high melt rates are realistic, the mass balance of Fimbulisen must be significantly negative, and the ice shelves along Dronning Maud Land must contribute about 4.4 mSv of melt water to the Weddell Sea, about 15% of the total Antarctic meltwater input to the Southern Ocean.
Keywords: Dronning Maud Land; Sørishavet; Weddellhavet; geofysikk; hydrografi; isshelf; oseanografi

Amundsen Sea ice production and transport - Assmann, Karen M.; Hellmer, Hartmut H.; Jacobs, Stanley S. (Journal of Geophysical Research: Oceans, 2005)
Drift and variability of sea ice in the Amundsen Sea are investigated with ice buoys deployed in March 2000 and a coupled ice-ocean model. The Bremerhaven Regional Ice Ocean Simulations (BRIOS) model results are compared with in situ ocean, atmosphere, and sea ice measurements; satellite observations; and 8?19 months of buoy drift data. We identify a zone of coastal westward drift and a band of faster eastward drift, separated by a broad transition region characterized by variable ice motions. The model represents drift events at scales approaching its resolution but is limited at smaller scales and by deficiencies in the National Centers for Environmental Prediction forcing. Two thirds of the modeled ice production in the southern Amundsen moves westward near the coast, its transport modulated by meridional wind strength, damping sea ice formation in the eastern Ross Sea. Half of the ice exported from the Ross moves eastward into the northern Amundsen Sea, a net sea ice sink that also receives more than one third of the ice generated to its south. A low rate of exchange occurs with the Bellingshausen Sea, which must have a more independent ice regime. Snow ice formation resulting from high precipitation accounts for one quarter of the ice volume in the Amundsen Sea, aiding the formation of thick ice in a region with generally divergent ice drift. Freshwater extraction by sea ice formation is roughly balanced by precipitation and ice shelf melting, but a positive trend in the surface flux is consistent with an Amundsen source for reported freshening in the Ross Sea.
Keywords: Amundsenhavet; Rosshavet; Sørishavet; geofysikk; havis; oseanografi

Cryosphere-hydrosphere interactions: Numerical modeling using the regional ocean Modeling System (ROMS) at different scales - Bergamasco, Andrea; Budgell, W. P.; Carniel, Sandro; Sclavo, Mauro (Il Nuovo cimento della Società Italiana di Fisica. C. Geophysics and space physics, 2005)
Conveyor belt circulation controls global climate through heat and water fluxes with atmosphere and from tropical to polar regions and vice versa. This circulation, commonly referred to as thermohaline circulation (THC), seems to have millennium time scale and nowadays-a non-glacial period-appears to be as rather stable. However, concern is raised by the buildup Of CO2 and other greenhouse gases in the atmosphere (IPCC, Third assessment report: Climate Change 2001, A contribution of working group I, II and III to the Third Assessment Report of the Intergovernmental Panel on Climate Change (Cambridge Univ. Press, UK) 2001, http://www.ipcc.ch) as these may affect the THC conveyor paths. Since it is widely recognized that dense-water formation sites act as primary sources in strengthening quasi-stable THC paths (Stommel H., Tellus, 13 (1961) 224), in order to simulate properly the consequences of such scenarios a better understanding of these oceanic processes is needed. To successfully model these processes, air-sea-ice-integrated modelling approaches are often required. Here we focus on two polar regions using the Regional Ocean Modeling System (ROMS). In the first region investigated, the North Atlantic-Arctic, where open-ocean deep convection and open-sea ice formation and dispersion under the intense air-sea interactions are the major engines, we use a new version of the coupled hydrodynamic-ice ROMS model. The second area belongs to the Antarctica region inside the Southern Ocean, where brine rejections during ice formation inside shelf seas origin dense water that, flowing along the continental slope, overflow becoming eventually abyssal waters. Results show how nowadays integrated-modelling tasks have become more and more feasible and effective; numerical simulations dealing with large computational domains or challenging different climate scenarios can be run on multi-processors platforms and on systems like LINUX clusters, made of the same hardware as PCs, and codes have been accordingly modified. This relevant numerical help coming from the computer science can now allow scientists to devote larger attention in the efforts of understanding the deep mechanisms of such complex processes.
Keywords: Sørishavet; geofysikk; klimaendringer; klimamodeller; oseanografi; polarområdene

Physical properties and stratigraphy of surface snow in western Dronning Maud Land, Antarctica - Kärkäs, Eija; Martma, Tõnu; Sonninen, Eloni (Polar Research, 2005)
Information about the spatial variations of snow properties and of annual accumulation on ice sheets is important if we are to understand the results obtained from ice cores, satellite remote sensing data and changes in climate patterns. The layer structure and spatial variations of physical properties of surface snow in western Dronning Maud Land were analysed during the austral summers 1999/2000, 2000/01 and 2003/04 in fi ve different snow zones. The measurements were performed in shallow (1 - 2 m) snow pits along a transect extending 350 km from the seaward edge of the ice shelf to the polar plateau. These pits covered at least the last annual accumulation and ranged in elevation from near sea level to 2500 m a.s.l. The ?18O values and accumulation rates had a good linear correlation with the distance from the coast. The mean accumulation on the ice shelf was 312 ± 28 mm water equivalent (w.e.); in the coastal region it was 215 ± 43 mm w.e. and on the polar plateau it was 92 ± 25 mm w.e. The mean annual conductivity and grain size values decreased exponentially with increasing distance from the ice edge, by 48 %/100 km and 18 %/100 km respectively. The mean grain size varied between 1.5 and 1.8 mm. Depth hoar layers were a common phenomenon, especially under thin ice crusts, and were associated with low dielectric constant values.
Keywords: Dronning Maud Land; geofysikk; geologi; havnivå; innlandsis; klimatologi; miljøendringer; overflatesnø; snø akkumulasjon; stratigrafi

A comparison of the NW European glaciated margin with other glaciated margins - Nielsen, Tove; De Santis, L.; Dahlgren, K.I. Torbjørn; Kuijpers, A.; Laberg, J.S.; Nygård, Atlé; Praeg, D.; Stoker, M.S. (The STRATAGEM Project, 2005)
The present paper provides an overview of glacial related seabed features and sedimentary sequences found along the formerly glaciated NW European margin and compare it with those found on contemporary glaciated margins from both the Southern and Northern Hemispheres. A brief review of the seabed physiography and strata architecture of the margins under consideration is followed by comparison of the most relevant similarities and differences. Comparison of the present-day bathymetric setting of both former and contemporary glaciated margins reveals no clear link to the effect of neither ice sheet or sediment load. Three different types of glacially eroded shelf transverse troughs have been identified, while marginal troughs seem connected to similar geological settings everywhere. Beyond the shelf edge interaction between downslope and alongslope processes has occurred resulting, amongst others, in the formation of large sedimentary mounds on the rise. More frequent large-scale mass wasting occurs on the former glaciated NW European margin than the Greenland and Antarctic margins in the latest Neogene to recent times. A two-stage evolution of the shelf prograding wedges is observed on all margins under consideration, which may reflect a general development of an ice cover from an initial phase of non- to restricted glaciation, evolving to a mature stage of expansive glaciation.
Keywords: Antarktis; geofysikk; marin geologi

Numerical simulation of three-dimensional, transient snow drifting around a cube - Beyers, Meiring; Sundsbø, Per Arne; Harms, Thomas M. (Journal of Wind Engineering and Industrial Aerodynamics, 2004)
This paper presents the results of the numerical simulation of drifting snow surrounding a simple 2m cubicle structure. These results are compared and verified against data from snow drifting experimental tests carried out at SANAE IV research station, Antarctica, during the summer research period of January 2002. In addition to the snow drifting field observations, wind profile data were also obtained from cup-type anemometers mounted on a 6m wind mast. These data were employed to derive the characteristic surface roughness, shear velocity and approaching wind profile functions. The present work numerically simulates a transient three-dimensional turbulent viscous flow in an Eulerian coordinate frame including snow advection. A modified turbulent wall law is employed that accounts for the effects of snow saltation on the effective aerodynamic surface roughness. The numerical simulation employed the commercial CFD code, FLOW-3D, with additional user Fortran coding added to model the snow entrainment, subsequent accumulation or erosion of snow as well as temporal snow surface changes. The snow accumulation and erosion model is presented and discussed. The snow accumulation predicted by this numerical simulation compares favourably with the experimental results obtained from the Antarctica field testing.
Keywords: Antarktis; forskningsstasjoner; geofysikk; ingeniørvitenskap; mekanikk; numerisk modellering

Slope failure dynamics and impacts from seafloor and shallow sub-seafloor geophysical data: case studies from the COSTA project - Canals, M.; Lastras, G.; Urgeles, R.; Casamor, J.L.; Mienert, Jürgen; Cattaneo, A.; De Batist, M.; Haflidason, Haflidi; Imbo, Y.; Laberg, J.S.; Locat, J.; Long, D.; et al. (COSTA - Continental Slope Stability, 2004)
Holocene and slightly pre-Holocene submarine landslide are found both in high-latitude glacial-dominated margins and in lower latitude, river-dominated margins. This paper constitutes a major assessment on some of the best-studied submarine instabilities in the world. We review and update from original data and literature reports the current state of knowledge of Storegga, Traenadjupet and Finneidfjord slides from the mid-Norwegian margin, Afen Slide from the Faeroe-Shetland Channel, BIG'95 Slide and Central Adriatic Deformation Belt (CADEB) from continental slope and inner continental shelf settings off the Ebro and Po rivers in the Mediterranean Sea, Canary Slide west of the westernmost, youngest Canary Islands and Gebra Slide off the northern tip of the Antarctic Peninsula in the southern hemisphere, i.e. those studied in the Continental Slope Stability (COSTA) project. The investigated slides range in size from the gigantic 90,000 km2 and almost 3000 km3 Storegga Slide to the tiny 1 km2 and 0.001 km3 Finneidfjord Slide. Not only do individual submarine landslides rarely involve processes precisely fitting with pre-established categories, mostly based on subaerial research, but also they display complex mechanical behaviors within the elastic and plastic fields. Individual events can involve simultaneous or successive vertical to translational movements including block detachment, block gliding, debris flow, mud flow and turbidity currents. The need for an in-depth revision of the classification criteria, and eventually for a new classification system, based on the new imaging capabilities provided by modern techniques, is more than obvious. We suggest a new system, which, for the moment, is restricted to debris flows and debris avalanches. Volume calculation methods are critically reviewed and the relations between some key geomorphic parameters are established for the selected slides. The assumed volume missing from scar areas does not necessarily match the actual volume of sediment remobilised by an individual event since in situ sediment can be remoulded and eventually incorporated during the slide downslope journey. CADEB, a shore-parallel prodelta detached from its source, is the exception to the good correlation found between across slope width and alongslope length with slide area. Height drop measured from the headwall upper rim to its foot correlates with the debris deposit maximum thickness unless the slide moves into restricted areas, which prevent farther forward expansion of the deposit, such as Gebra and BIG'95. In such cases, “over-thickened” deposits are found. A particularly loose and fluid behavior can be deduced for slides showing an “over-thinned” character, such as the Canary Slide that traveled 600 km. Scar areas and slip planes have been investigated with particular emphasis. Although slide headwalls might present locally steep gradients (up to 23° for Storegga Slide), the slope gradients of both the failed segment margins and the main slip planes are very low (max. 2° and usually around 1° and less). An exception is the Finneidfjord Slide (20°–<5°) that occurred in 1996 because of a combination of climatic and anthropogenic factors leading to excess pore pressure and failure. Mechanically distinct, low permeable clayey “weak layers” often correspond to slip planes beyond the slide headwall. Since not only formation of these “weak layers” but also sedimentation rates are climatically controlled, we can state that slide pre-conditioning is climatically driven too. Run-out distances reflect the degree of disintegration of the failed mass of sediment, the total volume of initially failed material and transport mechanisms, including hydroplanning. Commonly, specific run-outs could be attributed to distinct elements, such as cohesive blocks and looser matrix, as nicely illustrated by the BIG'95 Slide. Total run-outs usually correspond to matrix run-outs since the coarser elements tend to rest at shorter distances. Outrunner blocks are, finally, a very common feature proving the ability of those elements to glide over long distances with independence of the rest of the failed mass. In addition to pre-conditioning factors related to geological setting and sedimentation conditions, a final trigger is required for submarine landslides to take place, which is most often assumed to be an earthquake. In high latitude margins, earthquake magnitude intensification because of post-glacial isostatic rebound has likely played a major role in triggering landslides. Although it cannot be totally ruled out, there is little proof, at least amongst the COSTA slides, that gas hydrate destabilisation or other processes linked to the presence of shallow gas have acted as final triggers.
Keywords: Antarktis; batymetri; geofysikk; marin geologi

The effect of diapycnal mixing on the ventilation and CFC-11 uptake in the Southern Ocean - Gao, Yongqi; Drange, Helge (Advances in Atmospheric Sciences, 2004)
The Miami Isopycnic Coordinate Ocean Model (MICOM) is used to investigate the effect of diapycnal mixing on the oceanic uptake of CFC-11 and the ventilation of the surface waters in the Southern Ocean (south of 45°S). Three model experiments are performed: one with a diapycnal mixing coefficientKd (m2 s−1) of 2 × 10−7/N (Expt. 1), one withKd = 0 (Expt. 2), and one withKd = 5 × 10−8/N (Expt. 3),N (s−1) is the Brunt-Väisälä frequency. The model simulations indicate that the observed vertical distribution of CFC-11 along 88°W (prime meridian at 0°E) in the Southern Ocean is caused by local ventilation of the surface waters and westward-directed (eastward-directed) isopycnic transport and mixing from deeply ventilated waters in the Weddell Sea region. It is found that at the end of 1997, the simulated net ocean uptake of CFC-11 in Expt. 2 is 25% below that of Expt. 1. The decreased uptake of CFC-11 in the Southern Ocean accounts for 80% of this difference. Furthermore, Expts. 2 and 3 yield far more realistic vertical distributions of the ventilated CFC-waters than Expt. 1. The experiments clearly highlight the sensitivity of the Southern Ocean surface water ventilation to the distribution and thickness of the simulated mixed layer. It is argued that inclusion of CFCs in coupled climate models could be used as a test-bed for evaluating the decadal-scale ocean uptake of heat and CO2.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; oseanografi; strømmodeller

Firn accumulation records for the past 1000 years on the basis of dielectric profiling of six cores from Dronning Maud Land, Antarctica - Hofstede, Coen M; Roderik, S W van de Wal; Kaspers, Karsten Adrian; van den Broeke, Michiel R; Karlöf, Lars; Winther, Jan-Gunnar; Isaksson, Elisabeth; Lappegard, Gante; Mulvaney, Robert; Oerter, Hans; Wilhelms, Frank (Journal of Glaciology, 2004)
This paper presents an overview of firn accumulation in Dronning Maud Land (DML), Antarctica, over the past 1000 years. It is based on a chronology established with dated volcanogenic horizons detected by dielectric profiling of six medium-length firn cores. In 1998 the British Antarctic Survey retrieved a medium-length firn core from western DML. During the Nordic EPICA (European Project for Ice Coring in Antarctica) traverse of 2000/01, a 160 m long firn core was drilled in eastern DML. Together with previously published data from four other medium-length ice cores from the area, these cores yield 50 possible volcanogenic horizons. All six firn cores cover a mutual time record until the 29th eruption. This overlapping period represents a period of approximately 1000 years, with mean values ranging between 43 and 71 mm w.e. The cores revealed no significant trend in snow accumulation. Running averages over 50 years, averaged over the six cores, indicate temporal variations of5%. All cores display evidence of a minimum in the mean annual firn accumulation rate around AD 1500 and maxima around AD 1400 and 1800. The mean increase over the early 20th century was the strongest increase, but the absolute accumulation rate was not much higher than around AD 1400. In eastern DML a 13% increase is observed for the second half of the 20th century.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; paleoklimatologi

Seasonal ventilation of the cavity beneath Filchner-Ronne Ice Shelf simulated with an isopycnic coordinate ocean model - Jenkins, Adrian; Holland, David M.; Nicholls, Keith W.; Schröder, Michael; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
The ocean cavity beneath Filchner-Ronne Ice Shelf is observed to respond to the seasonal cycle of water mass production on the continental shelf of the southern Weddell Sea. Here we use a numerical model to investigate the propagation of newly formed shelf waters into the cavity. We find that the model reproduces the most distinctive features of the observed seasonality and offers a plausible explanation for those features. The most saline shelf waters are produced in the far west, where the inflow to the cavity peaks twice each year. The major peak occurs during the short period around midwinter when convection reaches full depth and the densest waters are generated. Once the surface density starts to decline, dynamic adjustment of the restratified water column leads to a gradual fall in the salinity at depth and a secondary peak in the inflow that occurs in summer at the western coast. Beneath the ice shelf the arrival of the wintertime inflow at the instrumented sites is accompanied by a rapid warming, while the slower decline in the inflow leads to a more gradual cooling. Water brought in by the secondary, summer peak flows mainly to the eastern parts of the cavity. Here the seasonality is suppressed because the new inflows mix with older waters that recirculate within a topographic depression. This pooling of waters in the east, where the primary outflow of Ice Shelf Water is generated, dampens the impact of seasonality on the local production of Weddell Sea Bottom Water.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi

Accumulation variability derived from an ice core from coastal Dronning Maud Land, Antarctica - Kaczmarska, Marzena; Isaksson, Elisabeth; Karlöf, Lars; Winther, Jan-Gunnar; Kohler, Jack; Godtliebsen, Fred; Olsen, Lena Ringstad; Hofstede, Coen M.; Van Den Broeke, Michiel R.; Van De Wal, Roderik S. W.; Gundestrup, Niels (Annals of Glaciology, 2004)
A 100 m long ice core was retrieved from the coastal area of Dronning Maud Land (DML), Antarctica, in the 2000/01 austral summer. The core was dated to AD 1737 by identification of volcanic horizons in dielectrical profiling and electrical conductivity measurement records in combination with seasonal layer counting from high-resolution oxygen isotope (δ18O) data. A mean long-term accumulation rate of 0.29 ma–1w.e. was derived from the high-resolution δ18O record as well as accumulation rates during periods in between the identified volcanic horizons. A statistically significant decrease in accumulation was found from about 1920 to the present. A comparison with other coastal ice cores from DML suggests that this is a regional pattern.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi

Analyses of firn gas samples from Dronning Maud Land, Antarctica: Study of nonmethane hydrocarbons and methyl chloride - Kaspers, Karsten Adrian; van de Wal, Roderick S. W.; de Gouw, Joost; Hofstede, Coen; van den Broeke, Michiel Roland; van der Veen, Carina; Neubert, Rolf; Meijer, Harro A. J.; Brenninkmeijer, Carl; Karlöf, Lars; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2004)
Firn air was sampled on the Antarctic plateau in Dronning Maud Land (DML), during the Norwegian Antarctic Research Expedition (NARE) 2000/2001. In this paper, we describe the analyses for methyl chloride and nonmethane hydrocarbons (NMHCs) in these firn air samples. For the first time, the NMHCs ethane, propane, and acetylene have been measured in Antarctic firn air, and concentration profiles for these gases have been derived. A one-dimensional numerical firn air diffusion model was used to interpret the measured profiles and to derive atmospheric concentrations as a function of time. The atmospheric trends we derived for the NMHC and methyl chloride at DML cover the period from 1975 to 2000. Methyl chloride shows a decreasing trend of 1.2 ± 0.6 ppt per year (annual mean concentration 548 ± 32 ppt). For ethane we found an increasing trend of 1.6 ± 0.6 ppt per year (annual mean concentration 241 ± 12 ppt). The concentrations of propane and acetylene appear to be constant over the period 1975–2000, with annual mean concentrations of 30 ± 4 ppt for propane and 24 ± 2 ppt for acetylene.
Keywords: Dronning Maud Land; NARE 2000/01; atmosfæren; gasskonsentrasjoner; geofysikk

Seasonal cycles of nonmethane hydrocarbons and methyl chloride, as derived from firn air from Dronning Maud Land, Antarctica - Kaspers, Karsten Adrian; van de Wal, Roderick S W; de Gouw, Joost; Hofstede, Coen; van den Broeke, Michiel; Reijmer, Carleen; van der Veen, Carina; Neubert, Rolf; Meijer, Harro A J; Brenninkmeijer, Carl; Karlöf, Lars; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2004)
This paper presents atmospheric concentrations of ethane, propane, acetylene, and methyl chloride, inferred from firn air by using a numerical one-dimensional firn diffusion model. The firn air was collected on the Antarctic plateau in Dronning Maud Land during the Norwegian Antarctic Research Expedition (NARE) 2000/2001. The influences of seasonal variations in temperature and pressure and the variation in accumulation rate were studied and are not negligible, but appear to cancel each other out if all variability is taken into account. This paper also demonstrates that firn air from the uppermost firn layer (30 m) can be used to derive seasonal cycles of these trace gases, without needing a year-round facility. These cycles display higher atmospheric mixing ratios during the Antarctic winter and lower atmospheric mixing ratios in summer. The cycles for the year 2000 show amplitudes of 140 ± 25 ppt for ethane, 30 ± 10 ppt for propane, 24 ± 6 ppt for acetylene, and 40 ± 20 ppt for methyl chloride. For ethane and propane the amplitudes and months of maximum atmospheric concentration (phase) are in reasonable agreement with year-round measurements at the South Pole and Baring Head (New Zealand). The amplitudes for methyl chloride and acetylene are significantly greater than seen in year-round measurements at the South Pole and at Neumayer (Antarctica), although the phase is in line. While biomass burning and removal by OH radicals can partially explain these large amplitudes, the exact cause still remains unclear for methyl chloride and acetylene.
Keywords: Dronning Maud Land; NARE 2000/01; atmosfæren; gasskonsentrasjoner; geofysikk; meteorologi

Circulation and water masses beneath the northern Ronne Ice Shelf, Antarctica - Nicholls, Keith W.; Makinson, Keith; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
We present oceanographic data from beneath the northern Ronne Ice Shelf. The data were collected during the austral summer of 2002–2003 from four sites located near the ice front in the Ronne Depression. They consist of conductivity-temperature-depth (CTD) profiles and time series from moored instruments that vary in length from 9 to 20 weeks. A strong, tidally modulated inflow of relatively fresh water was found at the eastern margin of the Ronne Depression. This low-density inflow powers high basal melt rates that are responsible for a substantially thinned area of ice shelf. A northward flow of Ice Shelf Water along the western margin of the depression (the Antarctic Peninsula coast) was inferred from the CTD data. From the new CTD and current meter data, and from published results from cruises along the ice front, we suggest that the flows at the margins of the Ronne Depression establish east-west density gradients that drive an anticyclonic circulation within the depression. The barotropic component of the circulation forms a gyre of strength 5 × 105 m3 s−1 and occupies a bowl in the field of water column thickness in the northern portion of the depression. All water masses sampled had temperatures below the surface freezing point and are therefore classified as Ice Shelf Water. The relatively complex nature of the oceanographic regime in the Ronne Depression is overlain by a seasonal variability that is hinted at by the available time series, probably explaining the apparent absence of inflowing HSSW at the time of the measurements.
Keywords: Antarktis; geofysikk; isfront; isshelf; oseanografi; vannmasser

Interannual variability and ventilation timescales in the ocean cavity beneath Filchner-Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2004)
Multiyear time series of ocean current and temperatures from beneath Filchner-Ronne Ice Shelf, Antarctica, demonstrate both seasonal and interannual variability. The seasonal signal is visible at all measurement sites, although it was swamped for a 2-year period (1999–2001) when extraordinarily light sea-ice cover in the southern Weddell Sea during the 1997–1998 Austral summer caused an anomalously large pulse of High Salinity Shelf Water to flush beneath the ice shelf. The pulse was observed twice at an instrumented site near the Berkner Island coast, once on its way to the Filchner Depression and once after the signal had propagated around the depression and returned to the site as an anomalously large pulse of Ice Shelf Water. The timings of the signal allow an estimate of 24–30 months for the flushing timescales of the sub-ice shelf ocean cavity, indicating that the cavity is highly responsive to external forcing. A timescale for the full ventilation of the cavity of 4–5 years is obtained from the length of time the sub-ice shelf conditions take to return to their original state, a timescale significantly shorter than previous estimates.
Keywords: Antarktis; Weddellhavet; geofysikk; havstrømmer; oseanografi

Measurements of ice thickness and seabed topography under the Fimbul Ice Shelf, Dronning Maud Land, Antarctica - Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2004)
This paper presents results from seismic measurements of the ice and water column thickness of the Fimbul Ice Shelf in the northeastern Weddell Sea. Seismic reflection measurements were conducted at 183 stations covering most of the ice shelf. Seismic velocities in the ice were derived from refraction measurements at 12 stations, distributed evenly across the area, as well as from temperature and density data from the Fimbul Ice Shelf. Velocities in the water were derived from temperature and salinity data from beneath the Fimbul Ice Shelf. Ice thicknesses were found to vary between 160 m and 550 m with uncertainties up to ±10 m. Water column thicknesses up to 900 m were found within the central ice shelf cavity, and values exceed 2000 m where the ice shelf overhangs the continental slope. Uncertainties in water column thickness are estimated to be ±60 m, and are dominated by the uncertainties in the shape of the seabed. Ice draft and seabed elevation was derived from ice and water column thickness assuming hydrostatic pressure. The resulting map of seabed elevation and water column thickness suggests that the strong westward flowing coastal current will be steered under the ice shelf and thus drive a sub-ice-shelf flow. Warm Deep Water does not have direct access to the ice shelf cavity, while relatively cold coastal waters shallower than 500 m will interact closely with the Fimbul Ice Shelf.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; isshelf; oseanografi

Improved Seismic Stratigraphy of the Mesozoic Weddell Sea - Rogenhagen, Johannes; Jokat, Wilfried; Hinz, Karl; Kristoffersen, Yngve (Marine Geophysical Researches, 2004)
We present a compilation of more than 45,000 km of multichannel seismic data acquired in the last three decades in the Weddell Sea. In accordance with recent tectonic models and available drillhole information, a consistent stratigraphic model for depositional units W1–W5 is set up. In conjunction with existing aeromagnetic data, a chronostratigraphic timetable is compiled and units W1.5, W2 and W3 are tentatively dated to have ages of between 136 Ma and 114 Ma. The age of W3 is not well constrained, but might be younger than 114 Ma. The data indicate that the thickest sediments are present in the western and southern Weddell Sea. These areas formed the earliest basins in the Weddell Sea and so the distribution of Mesozoic sediments is in accordance with the tectonic development of the ocean basin. In terms of Cenozoic glacial sediments, the largest depocenters are situated in front of the Filchner–Ronne Shelf, i.e. at the Crary Fan, with a thickness of up to 3 km.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi; seismologi; stratigrafi; tektonikk

Frazil ice formation in an ice shelf water plume - Smedsrud, Lars H.; Jenkins, Adrian (Journal of Geophysical Research: Oceans, 2004)
We present a model for the growth of frazil ice crystals and their accumulation as marine ice at the base of Antarctic ice shelves. The model describes the flow of buoyant water upward along the ice shelf base and includes the differential growth of a range of crystal sizes. Frazil ice formation starts when the rising plume becomes supercooled. Initially, the majority of crystals have a radius of ?0.3 mm and concentrations are below 0.1 g/L. Depending on the ice shelf slope, which controls the plume speed, frazil crystals increase in size and number. Typically, crystals up to 1.0 mm in radius are kept in suspension, and concentrations reach a maximum of 0.4 g/L. The frazil ice in suspension decreases the plume density and thus increases the plume speed. Larger crystals precipitate upward onto the ice shelf base first, with smaller crystals following as the plume slows down. In this way, marine ice is formed at rates of up to 4 m/yr in some places, consistent with areas of observed basal accumulation on Filchner-Ronne Ice Shelf. The plume continues below the ice shelf as long as it is buoyant. If the plume reaches the ice front, its rapid rise produces high supercooling and the ice crystals attain a radius of several millimeters before reaching the surface. Similar ice crystals have been trawled at depth north of Antarctic ice shelves, but otherwise no observations exist to verify these first predictions of ice crystal sizes and volumes.
Keywords: Antarktis; geofysikk; glasiologi; numerisk modellering; oseanografi

Some features of electron density behaviour in the high latitude D-region derived from in situ measurements - Danilov, A.D.; Smirnova, N.V.; Blix, Tom Arild; Thrane, E.V.; Vanina, L.B. (Journal of Atmospheric and Solar-Terrestrial Physics, 2003)
A large database of rocket measurements of the D-region electron concentration has been studied. The data were obtained at four sites in the Antarctic (Molodezhnaya and Syowa) and Arctic (Heiss Island, and Andøya/Kiruna). The electron densities were analysed in terms of their variations with solar zenith angle, geomagnetic activity and atmospheric temperature. We found that there is a particle ionisation source in the auroral oval even in quiet conditions. The energy of the particles is such, that they penetrate down to 85km, are partially absorbed between 85 and 80km but do not penetrate (are completely absorbed) below 75km. Analysis of the dependence of the electron concentration [e] on the daily sum of Kp indices, ∑Kp, shows that at all heights considered there is an increase of [e] with ∑Kp up to some saturation value of ∑Kp and beyond this level [e] is either constant (with large scatter of the data) or even decreases. This indicates that when the auroral oval expands with increasing geomagnetic activity, a particular station may move from a position outside or at the boundary of the oval, to a position inside the polar cap. An attempt is made to find the temperature dependence of the electron concentration. It is found that [e] at 75 and 80km increases with temperature T. Analysis of the flights conducted during noctilucent cloud (NLC) events at Andøya/Kiruna reveals a strong dependence of [e] on ∑Kp at 80 and 85km. This dependence is stronger and better defined than that for the entire data set. This may be explained by the low mesopause temperatures observed in summer when NLC occur. A comparison of the electron density data sets with empirical and theoretical models is presented and during quiet magnetic conditions a good agreement with mid-latitude models is found.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

A hindcast simulation of Arctic and Antarctic sea ice variability, 1955-2001 - Fichefet, Thierry; Goosse, Hugues; Morales Maqueda, Miguel Angel (Polar Research, 2003)
A hindcast simulation of the Arctic and Antarctic sea ice variability during 1955–2001 has been performed with a global, coarse resolution ice–ocean model driven by the National Centers for Environmental Prediction / National Center for Atmospheric Research reanalysis daily surface air temperatures and winds. Both the mean state and variability of the ice packs over the satellite observing period are reasonably well reproduced by the model. Over the 47-year period, the simulated ice area (defined as the total ice-covered oceanic area) in each hemisphere experiences large decadal variability together with a decreasing trend of ~1 % per decade. In the Southern Hemisphere, this trend is mostly caused by an abrupt retreat of the ice cover during the second half of the 1970s and the beginning of the 1980s. The modelled ice volume also exhibits pronounced decadal variability, especially in the Northern Hemisphere. Besides these fluctuations, we detected a downward trend in Arctic ice volume of 1.8 % per decade and an upward trend in Antarctic ice volume of 1.5 % per decade. However, caution must be exercised when interpreting these trends because of the shortness of the simulation and the strong decadal variations. Furthermore, sensitivity experiments have revealed that the trend in Antarctic ice volume is model-dependent.
Keywords: Sørishavet; forskning; geofysikk; havis; observasjoner; polarområdene; satellitt; sjøis

Description and evaluation of the bergen climate model: ARPEGE coupled with MICOM - Furevik, Tore; Bentsen, Mats; Drange, Helge; Kindem, I. K. T.; Kvamstø, Nils Gunnar; Sorteberg, Asgeir (Climate Dynamics, 2003)
A new coupled atmosphere–ocean–sea ice model has been developed, named the Bergen Climate Model (BCM). It consists of the atmospheric model ARPEGE/IFS, together with a global version of the ocean model MICOM including a dynamic–thermodynamic sea ice model. The coupling between the two models uses the OASIS software package. The new model concept is described, and results from a 300-year control integration is evaluated against observational data. In BCM, both the atmosphere and the ocean components use grids which can be irregular and have non-matching coastlines. Much effort has been put into the development of optimal interpolation schemes between the models, in particular the non-trivial problem of flux conservation in the coastal areas. A flux adjustment technique has been applied to the heat and fresh-water fluxes. There is, however, a weak drift in global mean sea-surface temperature (SST) and sea-surface salinity (SSS) of respectively 0.1 °C and 0.02 psu per century. The model gives a realistic simulation of the radiation balance at the top-of-the-atmosphere, and the net surface fluxes of longwave, shortwave, and turbulent heat fluxes are within observed values. Both global and total zonal means of cloud cover and precipitation are fairly close to observations, and errors are mainly related to the strength and positioning of the Hadley cell. The mean sea-level pressure (SLP) is well simulated, and both the mean state and the interannual standard deviation show realistic features. The SST field is several degrees too cold in the equatorial upwelling area in the Pacific, and about 1 °C too warm along the eastern margins of the oceans, and in the polar regions. The deviation from Levitus salinity is typically 0.1 psu – 0.4 psu, with a tendency for positive anomalies in the Northern Hemisphere, and negative in the Southern Hemisphere. The sea-ice distribution is realistic, but with too thin ice in the Arctic Ocean and too small ice coverage in the Southern Ocean. These model deficiencies have a strong influence on the surface air temperatures in these regions. Horizontal oceanic mass transports are in the lower range of those observed. The strength of the meridional overturning in the Atlantic is 18 Sv. An analysis of the large-scale variability in the model climate reveals realistic El Niño – Southern Oscillation (ENSO) and North Atlantic–Arctic Oscillation (NAO/AO) characteristics in the SLP and surface temperatures, including spatial patterns, frequencies, and strength. While the NAO/AO spectrum is white in SLP and red in temperature, the ENSO spectrum shows an energy maximum near 3 years.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; polarområdene

Numerical simulation: The Antarctic - Grønås, Sigbjørn; Raustein, Elmer; Heinemann, Guenther (Polar lows : mesoscale weather systems in the polar regions, 2003)
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Postglacial marine environmental changes in Maxwell Bay, King George Island, West Antarctica - Khim, Boo-Keun; Yoon, Ho Il (Polar Research, 2003)
Sediment textural properties and total organic carbon (TOC) contents of three sediment cores from Maxwell Bay, King George Island, West Antarctica, record changes in Holocene glaciomarine sedimentary environments. The lower sedimentary unit is mostly composed of TOC-poor diamictons, indicating advanced coastal glacier margins and rapid iceberg discharge in proximal glaciomarine settings with limited productivity and meltwater supply. Fine-grained, TOC-rich sediments in the upper lithologic unit suggest more open water and warm conditions, leading to enhanced biological productivity due to increased nutrient-rich meltwater supply into the bay. The relationship between TOC and total sulfur (TS) indicates that the additional sulfur within the sediment has not originated from in situ pyrite formation under the reducing condition, but rather may be attributed to the detrital supply of sand-sized pyrite from the hydrothermal-origin, quartz-pyrite rocks widely distributed in King George Island. The evolution of bottom-water hydrography after deglaciation was recorded in the benthic foraminiferal stable-isotopic composition, corroborated by the TOC and lithologic changes. The Ø18O values indicate that bottom-water in Maxwell Bay was probably mixed gradually with intruding 18O-rich seawater from Bransfield Strait. In addition, the Ø13C values reflect a spatial variability in the carbon isotope distribution in Maxwell Bay, depending on marine productivity as well as terrestrial carbon fluxes by meltwater discharge. The distinct lithologic transition, dated to approximately 8000 yr BP (uncorrected) and characterized by textural and geochemical contrasts, highlights the postglacial environmental change by a major coastal glacier retreat in Maxwell Bay.
Keywords: Sørishavet; geofysikk; geokjemi; marin geologi; miljøendringer; sedimenter

Water mass modification over the continental shelf north of Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Padman, Laurie; Schröder, Michael; Woodgate, Rebecca A.; Jenkins, Adrian; Østerhus, Svein (Journal of Geophysical Research: Oceans, 2003)
We use new data from the southern Weddell Sea continental shelf to describe water mass conversion processes in a formation region for cold and dense precursors of Antarctic Bottom Water. The cruises took place in early 1995, 1998, and 1999, and the time series obtained from moored instruments were up to 30 months in length, starting in 1995. We obtained new bathymetric data that greatly improve our definition of the Ronne Depression, which is now shown to be limited to the southwestern continental shelf and so cannot act as a conduit to northward flow from Ronne Ice Front. Large-scale intrusions of Modified Warm Deep Water (MWDW) onto the continental shelf occur along much of the shelf break, although there is only one location where the MWDW extends as far south as Ronne Ice Front. High-Salinity Shelf Water (HSSW) produced during the winter months dominates the continental shelf in the west. During summer, Ice Shelf Water (ISW) exits the subice cavity on the eastern side of the Ronne Depression, flows northwest along the ice front, and reenters the cavity at the ice front's western limit. During winter the ISW is not observed in the Ronne Depression north of the ice front. The flow of HSSW into the subice cavity via the Ronne Depression is estimated to be 0.9 ± 0.3 Sv. When combined with inflows along the remainder of Ronne Ice Front (reported elsewhere), sufficient heat is transported beneath the ice shelf to power an average basal melt rate of 0.34 ± 0.1 m yr−1.
Keywords: AABW; Sørishavet; Weddellhavet; geofysikk; havstrømmer; isshelf; kontinentalsokkel; oseanografi

Radionuclides deposition over Antarctica - Pourchet, Michel; Magand, Olivier; Frezzotti, Massimo; Ekaykin, Alexey A.; Winther, Jan Gunnar (Journal of Environmental Radioactivity, 2003)
A detailed and comprehensive map of the distribution patterns for both natural and artificial radionuclides over Antarctica has been established. This work integrates the results of several decades of international programs focusing on the analysis of natural and artificial radionuclides in snow and ice cores from this polar region. The mean value (37±20 Bq m−2) of 241Pu total deposition over 28 stations is determined from the gamma emissions of its daughter 241Am, presenting a long half-life (432.7 yrs). Detailed profiles and distributions of 241Pu in ice cores make it possible to clearly distinguish between the atmospheric thermonuclear tests of the fifties and sixties. Strong relationships are also found between radionuclide data (137Cs with respect to 241Pu and 210Pb with respect to 137Cs), make it possible to estimate the total deposition or natural fluxes of these radionuclides. Total deposition of 137Cs over Antarctica is estimated at 760 TBq, based on results from the 90–180° East sector. Given the irregular distribution of sampling sites, more ice cores and snow samples must be analyzed in other sectors of Antarctica to check the validity of this figure.
Keywords: Antarktis; geofysikk; geologi; glasiologi; radioaktivitet

Forecasting of polar lows : aspects of forecasting specific to the Antarctic - Rasmussen, Erik A; Turner, John; Røsting, Bjørn (Polar lows : mesoscale weather systems in the polar regions, 2003)
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Sea ice formation on a very cold surface - Smedsrud, Lars Henrik; Saloranta, Tuomo; Haugan, Peter M; Kangas, Tor-Villy (Geophysical Research Letters, 2003)
In this study laboratory experiments of sea ice formed on a vertical surface with initial temperature of −30 to −50°C are presented. The ice formation is rapid, and in 300 s >5 mm of sea ice is formed. Ice formation cooled and salinified the water, and induced a vertical down wards flow of ∼5 mm/s with a boundary layer about 5 mm thick. This ice has a structure with columnar crystals that have small circular cross sections (0.2–1.0 mm) and sea ice salinities are between 24 and 32. A simple model approach indicate that the thermal conductivity of such ice is lower than for other types of sea ice.
Keywords: Antarktis; geofysikk; glasiologi; havis; innlandsis; isshelf; laboratorieeksperimenter; polarområdene; sjøis

Renewal time and transport of unventilated Central Intermediate Water of the Weddell Sea derived from biogeochemical properties - Hoppema, Mario; de Baar, Hein J. W.; Fahrbach, Eberhard; Bellerby, Richard G. J. (Journal of Marine Research, 2002)
We have investigated the intermediate water mass of the central Weddell Gyre using TCO2 and oxygen data of FS Polarstern cruises in 1992, 1996 and 1998. This water mass, designated as Central Intermediate Water (CIW), is enriched in CO2 and depleted in O-2 relative to its source water due to biological degradation. CO2 enrichment and O-2 depletion were quantified by calculating the difference between the concentrations in the CIW and those in the, more southern source water, the Circumpolar Deep Water, which derives from the Antarctic Circumpolar Current. Inventories of enrichment and depletion were determined over the whole depth range of CIW, i.e. about 200800 m. The O-2 depletion inventory was greater than that of TCO2 enrichment which is in line with a biological origin of the signal. Spatial and interannual variation appeared to be small. Because subsurface remineralization in the central Weddell Gyre is largely restricted to the CIW, the export production estimate from previous work has been applied to compute the renewal time of CIW from these inventories. A renewal time of only three years was found. TCO2- and O-2-based computations were consistent, the former showing larger variation, though. From renewal time and volume of the CIW, a transport velocity (renewal rate) of 6-7 Sv was obtained. Of this, about I Sv is upwelled into the surface layer. The remaining 5-6 Sv CIW must be exported to the north, which is opposite to previous views. Results of water mass age and transport rate have thus been obtained using a method based on biogeochemical parameters. As the CIW cannot be identified by temperature and salinity, nor with transient tracers because it is hardly ventilated, this is the only way to obtain such results. As part of the CIW export, a large amount of remineralized CO2 enters the abyssal oceans where it is sequestered for long periods of time. The CIW is a principal and highly efficient player in the biological pump mechanism of the Southern Ocean.
Keywords: AABW; Sørishavet; Weddellhavet; biogeokjemi; geofysikk; havstrømmer; oseanografi; vannmasser

Annual export production in the interior Weddell Gyre estimated from a chemical mass balance of nutrients - Hoppema, Mario; de Baar, Hein J.W.; Bellerby, Richard G.J.; Fahrbach, Eberhard; Bakker, Karel (The Southern Ocean I: Climatic Changes in the Cycle of Carbon in the Southern Ocean, 2002)
Nitrate, phosphate and silicate data are presented from 1992 austral winter and 1998 austral autumn cruises with “FS Polarstern” in the Weddell Gyre. Because in the Weddell Gyre, away from the boundary current, the surface layer is eventually formed from upwelled deep water, the difference in nutrient concentrations between these layers can be used to compute net nutrient consumptions (identical with the export production). This method renders a value for the export production that is based on observed annual changes. The results are consistent for two years and two regions within the central gyre. The calculated net nitrate and phosphate consumptions were scaled to net carbon consumptions using canonical Redfield ratios, yielding 16–17μmolCkg−1yr−1. This equals 21±4gCm−2yr−1 as a robust estimate for the marginal ice zone. The net annual silicate consumption in the surface layer, which equals the export of biogenic silica, amounts to 15–18μmolkg−1yr−1. There is a tendency for higher values in the eastern Weddell Gyre. The estimated silicate consumption of about 1.8molSim−2yr−1 is relatively high compared to earlier estimations of biogenic silica export. The silicate to carbon consumption ratio of about 1 is very high, and documents the dominance of diatoms in the export of organic material. Résumé Sont présentées les distributions verticales de nitrate, de phosphate et de silicate en Mer de Weddell, pour les périodes de l’hiver austral 1992 et de l’automne austral 1998. Les eaux de surface du tourbillon à grande échelle de la Mer de Weddell (temps de résidence égal à 2.9 ans) sont formées par l’upwelling des eaux profondes. La différence de concentrations des sels nutritifs entre les couches profondes et de surface permettent de calculer la consommation annuelle, équivalente à la production exportée de l’élément nutritif considéré vers les couches profondes. Les résultats sont comparables pour les deux scénarios annuels étudiés. La production exportée de carbone pour les eaux de surface de la zone marginale de la glace, calculée à partir des consommations annuelles en nitrates et phosphates après transformation grâce aux rapports de Redfield, est estimée à 16–17μmolCkg−1yr−1 soit en moyenne 21±4gCm−2yr−1. La consommation annuelle de silicate est estimée à 1.8mol Si m−2yr−1, relativement élevée en comparaison des estimations antérieures. Le rapport molaire Si/C, voisin de 1 dans le matériel exporté, traduit la dominance des diatomées dans l’export de matières organiques.
Keywords: Sørishavet; Weddellhavet; fytoplankton; geofysikk; karbondioksid; marin biologi; oseanografi

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi

Electron density variations in the upper D region at high latitudes according to in situ measurements - Danilov, Alexey; Smirnova, N.V.; Vanina-Dart, Liudmila; Blix, Tom Arild; Thrane, Eivind (Geomagnetism and Aeronomy, 2001)
A large set of rocket measurements of the electron concentration [e] in the upper D region at four rocket sites (Molodezhnaya (Antarctic), Heiss Island (Arctic), Syowa (Antarctic), and Andoya/Kiruna (Arctic)) is considered. The dependence of [e] on the solar zenith angle X and geomagnetic activity index ∑Kp is analyzed. It has been shown that, the spread in [e] values reaches two orders of magnitude at any assigned value of χ. Nevertheless, it is possible to draw a lower envelope for the entire set of points and to obtain the [e] variation with χ in undisturbed conditions. In an analysis of the envelopes, it is seen that a corpuscular ionization source (presumably, electrons with an energy of above 40 keV) exists in the nonsunlit D region even in quiet conditions. An analysis of the electron concentration dependence on the daily sum of ∑Kp indices (∑Kp) shows that, at all heights considered, increases [e] with increasing ∑Kp to a certain boundary value ∑Kp and then remains either constant (with a rather wide spread in the data) or even decreases. This saturation effect may be caused by the auroral oval equatorward motion. As a result of this motion the site position may change: it may move toward the boundary between the auroral oval and polar cap or even be within the latter. The slope k of the [e] variation plotted versus ∑Kp at different χ is considered. It is shown that k grows with increasing χ and is maximal at χ> 100°.
Keywords: Antarktis; geofysikk; geomagnetiske stormer; ionosfæren; meteorologi; polarområdene

Direct measurements reveal insignificant storage of anthropogenic CO2 in the Abyssal Weddell Sea - Hoppema, Mario; Roether, Wolfgang; Bellerby, Richard G. J.; de Baar, Hein J. W. (Geophysical Research Letters, 2001)
In the northern Weddell Gyre at the prime meridian, Total TCO2 changes in the Weddell Sea Bottom Water (WSBW) have been investigated. Following a suggestion by [Poisson and Chen, 1987], the TCO2 difference at potential temperatures of 0.2°C and −0.8°C was determined using data from 1996 and 1998. No significant difference was found to similar differences for the years 1973 and 1981 reported by Poisson and Chen. Thus, over a period of 25 years an at most minor amount of anthropogenic CO2 has penetrated into the WSBW at this location. This suggests that this abyssal subpolar region is relatively unimportant for the storage of anthropogenic CO2. The same core of WSBW exhibited a marked increase of chlorofluorocarbon (CFC). For the Southern Ocean, therefore, CFCs are apparently of limited value as analogues of anthropogenic CO2, in contrast to some other ocean provinces.
Keywords: Sørishavet; Weddellhavet; antropogenisk CO2; drivhusgasser; geofysikk; klimagasser

Tropospheric response to stratospheric ozone loss - Kindem, Ina T; Christiansen, Bo (Geophysical Research Letters, 2001)
The response to realistic total column ozone trends on the troposphere and the stratosphere as simulated by the ARPEGE General Circulation Model (GCM) has been investigated. In both hemispheres, the lower stratosphere cooled and the polar vortex strengthened significantly during spring/early summer. The cooling trend was weaker than the observed trend in the Northern Hemisphere (NH), but stronger than the observed trend in the Southern Hemisphere (SH). In the troposphere, the changes in geopotential height resembled the positive phase of the Arctic Oscillation (AO) in the NH in March and the positive phase of the Antarctic Oscillation (AAO) in the SH during summer (December–February).
Keywords: Antarktis; geofysikk; meteorologi; ozonhull; ozonlaget

Oceanographic conditions south of Berkner Island, beneath Filchner-Ronne Ice Shelf, Antarctica - Nicholls, Keith William; Østerhus, Svein; Makinson, Keith; Johnson, Michaela R. (Journal of Geophysical Research: Oceans, 2001)
We have made oceanographic measurements at two sites beneath the southern Filchner-Ronne Ice Shelf. Hot-water drilled access holes were made during January 1999, allowing conductivity-temperature-depth (CTD) profiling and the deployment of instrument moorings. The CTD profiles show that the entire water column is below the surface freezing point. We estimate the (summer) flux of water between the two sites to be 2×106 m3 s−1. The summer potential temperature-salinity properties of the water column suggest that this flow is part of a recirculation in the deepest part of the subice shelf cavity and the Filchner Depression. The recirculation is driven by a combination of the melting of deep basal ice and the freezing that results from the depressurization of the cold buoyant water as it ascends the ice shelf base. The source of the water was high-salinity shelf water (HSSW) produced in the Ronne Depression. This is the water that provides the external heat necessary for the strong melting at the deep grounding lines in the vicinity of Foundation Ice Stream. Instruments moored at the drill sites show that during the winter HSSW formed on the Berkner Shelf flows beneath the ice shelf and largely displaces the recirculating water from the two sites. This provides an externally driven through flow that is warmer (nearer the surface freezing point) and slower than the internal recirculation and which is low enough in density to escape the Filchner Depression.
Keywords: Antarktis; geofysikk; havstrømmer; oseanografi

A 1500 year record of accumulation at Amundsenisen western Dronning Maud Land, Antarctica, derived from electrical and radioactive measurements on a 120 m ice core - Karlöf, Lars; Winther, Jan-Gunnar; Isaksson, Elisabeth; Kohler, Jack; Pinglot, Jean Francis; Wilhelms, Frank; Hansson, Margareta; Holmlund, Per; Nyman, M; Pettersson, Rikard; Stenberg, Malin; Thomassen, M P A; et al. (Journal of Geophysical Research: Atmospheres, 2000)
During the Nordic EPICA pre-site survey in Dronning Maud Land in 1997/1998 a 120 m long ice core was retrieved (76°00′S 08°03′W, 2400 m above sea level). The whole core has been measured using the electric conductivity measurement (ECM) and dielectric profiling (DEP) techniques, and the core chronology has been established by detecting major volcanic eruptions. In a nearby shallow core radioactive traces from nuclear tests conducted during the 1950s and 1960s have been identified. Altogether, 13 ECM and DEP peaks in the long core are identified as originating from specific volcanic eruptions. In addition two peaks of increased total β activity are identified in the short core. Accumulation is calculated as averages over the time periods between these dated events. Accumulation rate is 62 millimetres (w. eq./yr) for the last 181 years (1816 A.D. to present) and 61 mm w. eq./yr for the last 1457 years (540 A.D. to present). Our record shows an 8% decrease in accumulation between 1452 and 1641 A.D. (i.e. part of the Little Ice Age), compared to the long-term mean.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; iskjerner; paleoklimatologi

Combined characterisation of GOME and TOMS total ozone measurements from space using ground-based observations from the NDSC - Lambert, J.-C.; Van Roozendael, M.; Simon, P.C.; Pommereau, J.-P.; Goutail, F.; Gleason, J.F.; Andersen, S.B.; Arlander, D.W.; Bui Van, N.A.; Claude, H.; de La Noë, J.; De Mazière, M.; et al. (Advances in Space Research, 2000)
Several years of total ozone measured from space by the ERS-2 GOME, the Earth Probe TOMS, and the ADEOS TOMS, are compared with high-quality ground-based observations associated with the Network for the Detection of Stratospheric Change (NDSC), over an extended latitude range and a variety of geophysical conditions. The comparisons with each spaceborne sensor are combined altogether for investigating their respective solar zenith angle (SZA) dependence, dispersion, and difference of sensitivity. The space- and ground-based data are found to agree within a few percent on average. However, the analysis highlights for both GOME and TOMS several sources of discrepancies: (i) a SZA dependence with TOMS beyond 80° SZA; (ii) a seasonal SZA dependence with GOME beyond 70° SZA; (iii) a difference of sensitivity with GOME at high latitudes; (iv) a difference of sensitivity to low ozone values between satellite and SAOZ sensors around the southern tropics; (v) a north/south difference of TOMS with the ground-based observations; and (vi) internal inconsistencies in GOME total ozone.
Keywords: Antarktis; fjernmåling; geofysikk; meteorologi; ozonlaget; polarområdene; satellitt observasjoner

Snow and blue-ice distribution patterns on the coastal Antarctic Ice Sheet - Liston, Glen E.; Winther, Jan-Gunnar; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut; Karlöf, Lars (Antarctic Science, 2000)
Surface patterns of alternating snow and blue-ice bands are found in the Jutulgryta area of Dronning Maud Land, Antarctica. The snow-accumulation regions exist in the lee of blue-ice topographic ridges aligned perpendicular to winter winds. The snow bands are c. 500–2000 m wide and up to several kilometres long. In Jutulgryta, these features cover c. 5000 km2. These alternating snow and blue-ice bands are simulated using a snow transport and redistribution model, SnowTran-3D, that is driven with a winter cycle of observed daily screen-height air temperature, humidity, and wind speed and direction. The snow-transport model is coupled to a wind model that simulates wind flow over the relatively complex topography. Model results indicate that winter winds interact with the ice topographic features to produce alternating surface patterns of snow accumulation and erosion. In addition, model sensitivity simulations suggest that subtle topographic variations, on the order of 5m elevation change over a horizontal distance of 1 to 1.5 km, can lead to snow-accumulation variations that differ by a factor of six. This result is expected to have important consequences regarding the choice of sites for ice-coring efforts in Antarctica and elsewhere.
Keywords: Dronning Maud Land; blåis; geofysikk; glasiologi; iskjerner

The importance of charged aerosols in the polar mesosphere in connection with Noctilucent Clouds and Polar Mesosphere Summer Echoes - Blix, Tom Arild (The Antarctic and Arctic Middle Atmospheres: Their Differences and Similarities, 1999)
A number of campaigns have been conducted in order to study Polar Mesosphere Summer Echos (PMSE) and Noctilucent Clouds (NLC) in the period 1991–1994. Several sounding rockets have been launched through these layers with measurements being performed on upleg as well as downleg. These include measurements of positive ions and electrons in both ram and wake positions, as well as measurements of charged aerosols in ram on upleg. In this paper we will review these measurements and make a preliminary classification of the data based upon the presence of PMSE and/or NLC. One of the mechanisms responsible for PMSE is the presence of neutral air turbulence in combination with a high Schmidt number. We will briefly discuss this type of echo using in situ rocket data. Differences and similarities of PMSE and NLC as observed both in the Arctic and the Antarctic will be discussed. Observations show that especially PMSE are much more frequent in the Arctic. This may be due to a difference in the water vapour content or the temperature at mesopause heights. Lack of data in the Antarctic makes it difficult to decide which of these two factors are the most important. More measurements, especially co-ordinated in situ and ground-based lidar and radar measurements, are needed to discuss the Arctic and Antarctic similarities and differences in further detail.
Keywords: Antarktis; astrofysikk; atmosfæren; geofysikk; mesosfæren; meteorologi; polarområdene

Below-surface ice melt on the coastal Antarctic ice sheet - Liston, Glen E; Winther, Jan-Gunnar; Bruland, Oddbjørn; Elverhøy, Hallgeir; Sand, Knut (Journal of Glaciology, 1999)
In the Jutulgryta area of Dronning Maud Land, Antarctica, subsurface melting of the ice sheet has been observed. The melting takes place during the summer months in blue-ice areas under conditions of below-freezing air and surface temperatures. Adjacent snow-covered regions, having the same meteorological and climatic conditions, experience little or no subsurface melting. To help explain and understand the observed melt-rate differences in the blue-ice and snow-covered areas, a physically based numerical model of the coupled atmosphere, radiation, snow and blue-ice system has been developed. The model comprises a heat-transfer equation which includes a spectrally dependent solar-radiation source term. The penetration of radiation into the snow and blue ice depends on the solar-radiation spectrum, the surface albedo and the snow and blue-ice grain-sizes and densities. In addition, the model uses a complete surface energy balance to define the surface boundary conditions. It is run over the full annual cycle, simulating temperature profiles and melting and freezing quantities throughout the summer and winter seasons. The model is driven and validated using field observations collected during the Norwegian Antarctic Research Expedition (NARE) 1996–97. The simulations suggest that the observed differences between subsurface snow and blue-ice melting can be explained largely by radiative and heat-transfer interactions resulting from differences in albedo, grain-size and density between the two mediums.
Keywords: Dronning Maud Land; NARE 1996/97; blåis; geofysikk; glasiologi; innlandsis

A global model tool for three-dimensional multiyear stratospheric chemistry simulations: Model description and first results - Rummukainen, Markku; Isaksen, Ivar S A; Rognerud, Bjørg; Stordal, Frode (Journal of Geophysical Research: Atmospheres, 1999)
The paper presents a new global modeling tool, Stratospheric Chemical Transport Model 2. It has been developed for effective three-dimensional multiyear stratospheric chemistry studies, featuring an extensive chemistry scheme, heterogeneous processing on sulfate aerosols, and some polar stratospheric cloud processes. The transport algorithm maintains sub-grid-scale distributions and connects vertically the stratospheric layers, even in a coarse vertical grid. The model has been integrated for 49 months, recycling 1 year of precalculated transport from a middle atmosphere general circulation model. One year of daily National Centers for Environmental Prediction global analyses are used as temperatures. Diurnal cycles of photolysis rates are recalculated every 7 days to give interaction with ozone changes. The model is able to describe most of the geographical and seasonal ozone variability and the meridional distributions of ozone, reactive nitrogen, chlorine, and bromine. Stratospheric diurnal cycles for nitrogen, hydrogen, chlorine, and bromine species are captured in detail. The upper stratosphere ozone deficiency, typical to models, is large. Its sensitivity to different ways of tuning are explored. Midlatitude, rather than polar, wintertime processes have so far been the focus in this model tool. The present transport and grid resolution are not suited for realistic simulations at high latitudes. As there is only a limited inclusion of polar stratospheric cloud (PSC) microphysics, chemical processing in the cold polar lower stratosphere also cannot be well simulated. For example, the Antarctic ozone hole is not simulated, but the modeled chemistry should be suitable for warm Arctic winters when type II PSCs and particle sedimentation do not occur.
Keywords: Antarktis; geofysikk; meteorologi; ozonlaget; polarområdene; stratosfæren; stratosfærisk kjemi

Estimate of the subglacier dielectric constant of an ice shelf using a ground-penetrating step-frequency radar - Hamran, Svein Erik; Erlingsson, Bjørn; Gjessing, Yngvar; Mo, Per (IEEE Transactions on Geoscience and Remote Sensing, 1998)
The mass balance of the Antarctic ice cap, its stability, and the role of the surrounding ice shelf in bottomwater mass formation is, to a large extent, dictated by processes associated with subsurface freezing and melting, where the submerged ice meets the surrounding ocean. It is demonstrated how multifrequency ground-penetrating radar data collected at the Riiser-Larsenisen can be used to examine the physical conditions of the ice-shelf subsurface. The received radar signal from three different frequency intervals, 10-30, 155-170, and 330-360 MHz (range of wavelengths from 15 to 0.5 m in the ice), was analyzed by using a plane reflector model. It is demonstrated that the data can be successfully used to distinguish between types of ice at the ice-ocean interface, such as for freezing marine ice, melting marine ice, melting meteoric ice from the ice cap, and melting firn/ice. The data analysis shows that the subsurface can be regarded as rough on length scales in the order of 1 m.
Keywords: Antarktis; brehylle; fjernanalyse; geofysikk; georadar; glasiologi; isbreer; isbrem; isshelf; oseanografi

Large spatial variation in accumulation rate in Jutulstraumen ice stream, Dronning Maud Land, Antarctica - Melvold, Kjetil; Hagen, Jon Ove; Pinglot, Jean Francis; Gunuestrup, Niels (Annals of Glaciology, 1998)
A mass-balance programme was initiated on Jutulstraumen ice stream, western Dronning Maud Land,Antarctica, during the austral summer 1992-93. As a part of the mass-balance programme, accumulation rate was measured along the centre line of Jutulstraumen from the shelf edge up to the plateau at about 2500 m a.s.l. Accumulation distribution obtained from seven shallow firn cores and 48 slake readings is presented. The overall net accumulation trend displays a decreasing accumulation with increasing elevation and distance to coast, but on both the mesoscale and microscale there are significant variations. This is due to complex patterns of precipitation controlled by orography and redistribution by katabatic winds. The local accumulation distribution (few km scale) was found to be dependent on downslope surface gradient (aspect north, northwest), and variations up to 100% were found over distances of less than 3 km. The large variation in accumulation is important when selecting new core sites and for interpretation of temporal and spatial variations in accumulation derived from firn cores.
Keywords: Dronning Maud Land; geofysikk; geografi; glasiologi; isstrøm

Stability of the Thermohaline Circulation to Noisy Surface Buoyancy Forcing for the Present and a Warm Climate in an Ocean General Circulation Model - Skagseth, Øystein; Mork, Kjell Arne (Journal of Physical Oceanography, 1998)
The stabilities of two different circulation regimes in the North Atlantic, 1) the present thermohaline circulation and 2) a weaker thermohaline circulation, are compared using the Hamburg Large Scale Geostrophic (LSG) ocean circulation model. The latter circulation regime is obtained by restoring the LSG model toward an on average 48C warmer air surface temperature corresponding to a doubled atmospheric content of CO 2 . The stabilities of these stationary states are investigated by imposing various amounts of stochastic noise on the surface freshwater flux. The simulations show more variability on secular timescales for the present than for the warm climate. Since the modeled static stabilities for the two climates are relatively similar, the different rates of variability are probably connected to other mechanisms. In the present climate at high latitudes the two buoyancy fluxes due to heat and freshwater are of similar magnitudes but with opposite signs; thus switches between convective and nonconvective periods at secular timescales are possible. In the warm climate the buoyancy flux due to heat dominates. This compensates the effect of the noisy freshwater forcing and thus reduces the potential for secular oscillations. The stronger coupling between the Atlantic and the Southern Ocean for the present relative to the warm climate could also contribute to this difference. Furthermore, the simulations show that the variability of the Antarctic Circumpolar Current transport for the present climate exceeds that of the warm climate. For increasing stochastic noise the present circulation approaches that of the warm circulation. The authors apply a mixture of heat flux and temperature restoring for the surface boundary condition. Comparison with similar works, which apply a pure restoring for surface temperature, shows that the ocean circulation is much less sensitive to forced stochastic freshwater anomalies with the type of boundary condition used herein. A box model is used to illustrate the effects of the surface temperature parameterizations and the different buoyancy forcing for the present and warm climate.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; polarområdene; vannmasser

Spatial variability of snow chemistry in western Dronning Maud Land, Antarctica - Stenberg, Malin; Isaksson, Elisabeth; Hansson, Margareta; Karlen, Wibjörn; Mayewski, Paul A.; Twickler, Mark S.; Whitlow, Sallie I.; Gundestrup, Niels (Annals of Glaciology, 1998)
During the austral summer of 1993-94 a number of 1-2 m deep snow pits were sampled in connection with firn-coring in western Dronning Maud Land, Antarctica. The traverse went from 800 to about 3000 m a.s.l. upon the high-altitude plateau. Profiles of cations (Na+, K+, Mg2+, Ca2+), anions (Cl−, NO3-, SO42- , CH3SO3−) and stable oxygen isotopes (δ18O) from 11 snow pils are presented here. Close to the coast 2 m of snow accumulates in about 2-3 years, whilst at sites on the high-altitude plateau 2 m of snow accumulates in 10—14 years. The spatial variation in ion concentrations shows that the ions can be divided into two groups, one with sea-salt elements and methane sulfonate and the other with nitrate and sulfate. For the sca-salt elements and methane sulfonate the concentrations decrease with increasing altitude and increasing distance from the coast, as well as with decreasing temperature and decreasing accumulation rate. For nitrate and sulfate the concentrations are constant or increase with respect to these parameters. This pattern suggests that the sources for sca-salt elements and methane sulfonate are local, whereas the sources for nitrate and sulfate are a mixture of local and long-range transport.
Keywords: Dronning Maud Land; geofysikk; geokjemi; glasiologi; iskjerner; meteorologi

Report of the Norwegian Antarctic Research Expedition 1992/93 - Orheim, Olav (ed.) (Norsk Polarinstitutt, 1997)
Keywords: Antarktis; NARE 1992/93; ekspedisjoner; geofysikk; geologi; glasiologi; marin biologi; marin geologi; ornitologi; oseanografi; topografi

Spatial distribution of snow in western Dronning Maud Land, East Antarctica, mapped by a ground-based snow radar - Richardson, Cecilia; Aarholt, Eldar; Hamran, Svein-Erik; Holmlund, Per; Isaksson, Elisabeth (Journal of Geophysical Research: Solid Earth, 1997)
During the austral summer 1993/1994, the spatial distribution of snow was mapped by a ground-based snow radar (800–2300 MHz) in western Dronning Maud Land, East Antarctica. Snow radar soundings were performed along continuous profiles extending from the ice shelf up to the polar plateau, a total distance of 1040 km. The high-resolution radar registrations revealed subsurface layering in the uppermost 12 m of the snowpack. The travel time record was translated into snow accumulation expressed in water equivalents, based on an empirical relationship between wave speed and firn density. A good knowledge on snow density variations with depth is essential for the variability studies. Generally, the snow layering was well developed in the coastal area and less well developed on the polar plateau. High spatial variability in snow accumulation was observed on a regional as well as on a local scale. The variability was very high in areas with large surface slopes, such as the grounding zone and around nunataks. The highest variability was recorded in the nunatak area, where the standard deviation reached 59% of the spatial average accumulation. On the smooth high-altitude plateau, variations in accumulation were less pronounced. However, here the standard deviation exceeded 22% of the average accumulation rate. Provided that the snow radar soundings are supported by dating of reference horizons along the travel route, this is a good method to obtain the accumulation rate and pattern for large areas with a high spatial resolution.
Keywords: Dronning Maud Land; fysisk geografi; geofysikk; geokjemi; glasiologi; iskjerner

Spatial and temporal variation of sublimation on Antarctica: Results of a high-resolution general circulation model - van den Broeke, Michiel R. (Journal of Geophysical Research: Atmospheres, 1997)
In this paper we use output of a high-resolution general circulation model (ECHAM-3 T106, resolution 1.1°?1.1°) to study the spatial and temporal variation of sublimation on Antarctica. First, we compare model results with available observations of sublimation rates. The yearly cycle, with small latent heat fluxes during the winter, is well reproduced, and the agreement with sparsely available spot observations is fair. The model results suggest that a significant 10?15% of the annual precipitation over Antarctica is lost through sublimation and that sublimation plays an important role in the formation of blue ice areas. A preliminary analysis of the atmospheric boundary layer moisture budget shows that the spatial variation of sublimation in the coastal zone of East Antarctica can be explained by variations of horizontal advection of dry air. Dry air advection, and thus surface sublimation, is enhanced in areas where katabatic winds are strong and have a large downslope component and where the Antarctic topography drops suddenly from the plateau to the coastal zone. In areas where horizontal advection is small, like the plateau and the large ice shelves, special conditions must be met to make significant sublimation at the surface possible.
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Modelling the ocean response to secular surface temperature transitions - Mork, K. A.; Skagseth, Øystein (Climate Dynamics, 1996)
The ocean response to surface temperature transients is simulated with the use of the Hamburg large-scale geostrophic (LSG) ocean general circulation model (OGCM). The transition, from the present to a climate corresponding to a doubling of the atmospheric CO2 content, is compared with the reversed transition. For the Atlantic, the time scale for the deep ocean to adjust to the temperature changes was similar for both transitions. In the Pacific, the time scale is shorter for the present to warm transition than for the reverse case, a result of increased production of Antarctic bottom water (AABW) during the warm climate. While the transition from cold to warm climate shows no secular variability, the reversed transition generates considerable variability on time scales of 300–400 years. For the warm climate, oscillations with periods of 45 years are found in the Southern Ocean. Results of principal oscillation pattern (POP) analysis indicate that these oscillations are due to interaction between convection in the Southern Ocean and advected salinity anomalies in the Antarctic Circumpolar Current (ACC) and the Southern Pacific Ocean.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; geofysikk; havstrømmer; oseanografi; vannmasser

Formation and circulation of Ice Shelf Water in the Weddell and Ross seas - Nøst, Ole Anders (University of Bergen, 1995)
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Distribution of Water Masses on the Continental Shelf in the Southern Weddell Sea - Gammelsrød, Tor; Foldvik, Arne; Nøst, Ole Anders; Foldvik, Ø.; Anderson, Leif G.; Fogelqvist, Elisabet; Olsson, K. Anders; Tanhua, Toste; Jones, Elizabeth Peter; Østerhus, Svein (The Polar Oceans and Their Role in Shaping the Global Environment, 1994)
Water properties on the continental shelf in the southern Weddell Sea observed during NARP 92/93 are presented. The station distribution includes a section close to the floating ice shelf from the Filchner Depression to the Antarctic Peninsula. Temperature, salinity, oxygen, silicate, CFC-ll and CFC-12 distributions are shown. Melting under the ice shelves, circulation systems, residence times, sediment/water interactions and bottom water formation are discussed. Ice Shelf Water (ISW), which is formed by cooling and melting below the floating ice shelf, seems to be about 10 years older than its parent water mass, which indicates the residence time below the ice shelf. The average melting rate below the Filchner Ronne ice shelf, based on the volume flux of ISW in the Filchner Depression is estimated to be 0.1 m/year. Compared with earlier observations considerable changes were found in the water characteristics and distribution: The temperature of the Weddell Deep Water has increased 0.7°C since 1977. Western Shelf Water, usually dominating the bottom layers in the Filchner Depression and on the Berkner Shelf, was found only in the Ronne Depression.
Keywords: NARP 1992/93; Sørishavet; Weddellhavet; geofysikk; oseanografi

A model of ice shelf-ocean interaction with application to the Filchner-Ronne and Ross Ice Shelves - Nøst, Ole Anders; Foldvik, Arne (Journal of Geophysical Research: Oceans, 1994)
A simple analytical model has been developed to study the formation of Ice Shelf Water (ISW). ISW is assumed to flow as a buoyancy-driven layer underneath the ice shelf. A relation between potential temperature and salinity in the ISW layer is calculated from the mass and energy balance. This temperature-salinity relation is shown to depend only on the temperature and the salinity of the source water mass and to be practically independent of entrainment and melt rates. The model results are obtained without making any assumptions about entrainment and melt rates. The model is in good agreement with observations under the Ronne Ice Shelf, and it indicates that ISW in the Filchner Depression is formed from Western Shelf Water (WSW) with salinity higher than 34.75 practical salinity units. Such high-salinity water is only observed in the Ronne Depression in the western part of the continental shelf. This implies a circulation of WSW, under the Filchner-Ronne Ice Shelf, from the Ronne Depression into the Filchner Depression. Similarly, the model shows that the ISW observed under J9 at the Ross Ice Shelf has been formed from Low Salinity Shelf Water (LSSW) from the eastern parts of the Ross Sea continental shelf. LSSW must therefore circulate under the eastern parts of the Ross Ice Shelf.
Keywords: Antarktis; geofysikk; isshelf; kontinentalsokkel; oseanografi

Bunnvannsstrømmer på kontinentalskråningen i Weddellhavet - Nordlund, Nina (Universitetet i Bergen, 1992)
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; havstrømmer; oseanografi

En modell for sirkulasjonen under isshelfene i Weddelhavet og Rosshavet - Nøst, Ole Anders (O. A. Nøst, 1992)
Keywords: Rosshavet; Sørishavet; Weddellhavet; geofysikk; oseanografi

Crustal development: Weddel Sea - Ross Sea region. Evolution of the Gondwana plate boundary in the Weddel Sea area - Kristoffersen, Yngve; Hinz, Karl (Geological evolution of Antarctica : proceedings of the Fifth International Symposium on Antarctic Earth Sciences, held at Robinson College, Cambridge, 23-28 August 1987, 1991)
Keywords: Antarktis; Weddellhavet; geofysikk; geologi; seismologi; tektonikk

Radio-echo investigations in Dronning Maud Land - Kennett, Michael (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; geofysikk; isshelf; isstrøm; klimaendringer

Oxygen 18 and helium as tracers of ice shelf water and water/ice interaction in the Weddell Sea - Schlosser, Peter; Bayer, Reinhold; Foldvik, Arne; Gammelsrød, Tor; Rohardt, Gerd; Münnich, Karl Otto (Journal of Geophysical Research: Oceans, 1990)
Oxygen 18 and helium isotope data from stations located in the Filchner Depression, on the continental slope of the southern Weddell Sea, and in the central Weddell Sea are presented and discussed. The 18O and 4He signals imprinted on the water circulating under the Filchner/Ronne Ice Shelf (Ice Shelf Water, or ISW) due to melting of glacial ice at the base of the ice shelf are traced across the sill separating the Filchner Depression from the Weddell Sea. Low δ18O values are correlated with high 4He concentrations in the ISW found in the Filchner Depression (minimum δ18O values: −0.8‰; maximum 4He concentrations: about 4.7×10−8 cm3 STP g−1). The fraction of glacial meltwater contained in the ISW found in the Filchner Depression is estimated to about 6 to 7‰. The 18O and helium isotope data from the overflowing shelf water component observed on the continental slope confirm the hypothesis that ISW contributes significantly to the Weddell Sea Bottom Water (WSBW). On the basis of a inultiparameter water mass analysis it is discussed which fraction of the WSBW originates from ISW and which other shelf waters potentially could contribute to WSBW.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; hydrografi; isbrem; isshelf; oseanografi; smeltevann; vannmasser

Anomalous palaeomagnetic directions in a Mesozoic basaltic dyke; arguments for fault-induced remagnetization - Løvlie, Reidar; Mitchell, John (Physics of the earth and planetary interiors, 1989)
Anomalously steep palaeomagnetic directions from the central part of an ∼ 5 m wide basaltic dyke from Fossilryggen, East Antarctica, suggest a Recent to late Tertiary age for its remanent magnetization, in conflict with KAr isotope ages of 162 ± 4 and 217 ± 3 Ma obtained from the central and slickenside margins respectively. Three neighbouring basaltic intrusions carry stable magnetizations whose directions (mean D, 23°; mean I, −40° and pole position, 38°N, 40°E) accord with previously obtained Mesozoic results from lava flows in the Vestfjella basalt province, East Antarctica. Rock magnetic properties do not discriminate between the different dykes, and it is proposed that the anomalous directions represent spot-readings of the geomagnetic field which arise from complete remagnetization during a period of faulting in Recent to late Tertiary times.
Keywords: Dronning Maud Land; NARE 1984/85; ekspedisjoner; geofysikk; geologi

Icebergs rework shelf sediments to 500 m off Antarctica - Barnes, Peter W.; Lien, Reidar (Geology, 1988)
Icebergs and sea ice rework the sediments of high-latitude shelves, producing modern diamicts (ice-keel turbates) unrelated to glacial proximity. Off Antarctica, sidescan sonar data indicate the presence of ice-gouge features formed by the physical interaction between ice keels and the sea bed. These are recognized as incisions a few metres deep and tens of metres wide, in water depths up to 500 m. On the submarine bank tops and slopes off Wilkes Land and in the Weddell Sea, subcircular depressions 30 to 150 m in diameter, a washboard pattern, and hummocky bed features also represent iceberg-resting sites. The freshness of sea-bed morphology, nearby Holocene sediment ponding, and active hydraulic sedimentary processes indicate that the sea floor is being reworked by iceberg keels. Tabular iceberg drafts in excess of 330 m have been measured, and modeling studies suggest that nontabular iceberg drafts of 500 m are possible. We conclude that a modern ice-keel turbate deposit in the form of a poorly stratified diamicton is probably widespread on that part (54%) of the Antarctic shelf less than 500 m deep.
Keywords: Sørishavet; Weddellhavet; geofysikk; geologi; isberg; issfjell; oseanografi

Notes on Southern Ocean hydrography, sea-ice and bottom water formation - Foldvik, Arne; Gammelsrød, Tor (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
The Southern Ocean circulation and sea-ice distribution is briefly described. The formation of extremely cold bottom water in the Weddell Sea and its relation to the floating Ronne-Filchner Ice Shelves is discussed. It is shown that a concentrated swift eroding bottom current with anomalous low ratio transports the cold and dense ice Shelf Water from the shelf towards large depths. Comments are made on possible implications of this process for the large-scale deep-water circulation and for the interpretation of sediment cores.
Keywords: Sørishavet; Weddellhavet; geofysikk; havis; havstrømmer; hydrografi; isshelf; oseanografi

Evidence for deuteric magnetization in hydrothermally altered Mesozoic basaltic rocks from East Antarctica - Løvlie, Reidar (Physics of the earth and planetary interiors, 1988)
Mesozoic basaltic lavas and dykes from Vestfjella, East Antarctica, are dominated by well-grouped, single-component palaeomagnetic directions of normal polarity. Reversed magnetizations, heavily overprinted by normal polarity components, were encountered in a few lava flows and dykes. Only thermal demagnetization was successful in separating tight distributions of reversed polarity directions, interpreted to represent a deuteric magnetization. The region has been exposed to regional hydrothermal alteration to the epidote/prehnite metamorphic facies (T ≈ 300°C). Titanomagnetite grains in high-temperature oxidation classes II–III show alteration features typical for hydrothermally altered basalts; partial to complete replacement of both ilmenite and magnetite to sphene is common in the most altered rocks, which also exhibit varying degrees of decomposition of the opaque minerals. The lavas display two major, but distinctly different, thermomagnetic curves; the ‘kink’ type, previously reported from rocks exposed to the epidote metamorphic facies, and curves dominated by a paramagnetic contribution defining a magnetite Curie point. It is concluded that the basalts have retained palaeomagnetic directions acquired during the deuteric cooling phase, implying that granulation/sphene formation and Fe depletion of decomposed titanomagnetite grains in classes II–III do not necessarily cause complete remagnetization or the acquisition of significant secondary remanent magnetizations.
Keywords: Dronning Maud Land; geofysikk; geokjemi; geologi

Temperature of active layer at Bunger Oasis in Antarctica in summer 1978-79 - Wójcik, Gabriel (Proceedings / Permafrost, Fifth International Conference, 1988)
Keywords: Antarktis; geofysikk; permafrost

Chemical weathering in permafrost regions of Antarctica: Great Wall Station of China, Casey Station and Davis Station of Australia - Xie, Youyu (Proceedings / Permafrost, Fifth International Conference, 1988)
Keywords: Antarktis; geofysikk; geokjemi

Geology, geophysics, and hydrocarbon potential of Antarctica continental margin of Weddell Sea - Hinz, K.; Kristoffersen, Yngve (AAPG Bulletin, 1987)
A prominent escarpment, called the Explora-Andenes Escarpment, has been recognized between long. 40°W, lat. 72°40^primeS and long. 10°W, lat. 69°20^primeS. It separates the continental margin from the Weddell Sea basin. Our recent MCS data have revealed the presence of some remarkably symmetric structures beneath a thick pile of tectonically undisturbed sediments. For example, two extensive wedge-shaped basement units occur between 20°W and 40°W. These units are characterized by a pattern of divergent reflectors which surround an elongated depression in basement. The northern wedge terminates against the Explora-Andenes Escarpment between 25°W and 30°W. The southern wedge, known as the Explora Wedge, shows a northward-dipping reflection pattern. The seismic characteristics suggest that both wedges consist of volcanic rocks. The basement depression is interpreted as a failed rift basin. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of "dipping reflectors." The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures. The initial fragmentation of Gondwana was accompanied by prolific volcanism, which led to the emplacement of the wedges of dipping reflectors. The tectonomagmatic/volcanic period was followed by transtensional movements between Africa and Antarctica. This phase was heralded by the formation of the Explora-Andenes Escarpment as a new plate boundary and the opening of the Weddell Sea by sea-floor spreading. The Explora-Andenes Escarpment cuts across the early rift structures.
Keywords: Antarktis; Sørishavet; Weddellhavet; geofysikk; geologi

Absolute movements, mass balance and snow temperatures of the Riiser-Larsenisen Ice Shelf, Antarctica - Gjessing, Yngvar; Wold, Bjørn (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Antarctic ozone depletion: 2-D model studies - Isaksen, Ivar S. A.; Stordal, Frode (Geophysical Research Letters, 1986)
Antarctic ozone depletion is estimated in a 2-D global model as a result of increase in chlorine levels from 1 ppb to 2.7 ppb and an increase in bromine levels from 15 ppt to 30 ppt. The adopted increase is assumed to be the anthropogenic influence on the stratospheric concentrations of chlorine and bromine species in 1985. Heterogeneous formation of ClO from the reaction between ClONO2 and HCl is included in the calculations, hypothesizing this is the dominant reaction path for chlorinated species on particle surfaces. A total ozone depletion as high as 14-20% may have occurred during the month of October at 80°S when maximum depletion is obtained. Both the magnitude and the time period when the maximum depletion occurs, agree with observed depletion over the last 8 years.
Keywords: Antarktis; geofysikk; meteorologi; ozonhull; ozonlaget

Geophysical evidence for the East Antarctic plate boundary in the Weddell Sea - Kristoffersen, Yngve; Haugland, Kristen (Nature, 1986)
An improved Gondwanaland reconstruction compatible with geological and geophysical information from the surrounding oceans and continents seems to require microplates to solve the enigmatic pre-early-Mesozoic tectonic relation between West and East Antarctica1. New multi-channel seismic reflection data from the southeastern Weddell Sea acquired during the 1984–85 Norwegian Antarctic Research Expedition (NARE) have outlined a linear WSW–ENE-trending basement ridge buried below the continental slope over a distance of 700 km. This structural high truncates the trend of the large sedimentary basins below the Filchner and Ronne ice shelves and may continue to within a few hundred kilometres of the Antarctic Penninsula. We interpret the basement ridge as part of the East Antarctic plate boundary during the break-up of Gondwana. The morphology and structure of this boundary show greater apparent similarity to a rifted or obliquely rifted margin than to the sheared margin which is predicted by current reconstructions2,3. A linear East Antarctic plate margin extending to the vicinity of the Antarctic Peninsula makes any post-rift micro-plate motion in the Weddell Embayment unlikely.
Keywords: Antarktis; NARE 1984/85; Weddellhavet; geofysikk; geologi; tektonikk

Oxygen isotopes and accumulation rates at Riiser-Larsenisen, Antarctica - Orheim, Olav; Gjessing, Yngvar; Lunde, Torbjørn; Repp, Kjell; Wold, Bjørn; Clausen, Henrik B; Liestøl, Olav (Glaciological research on Riiser-Larsenisen and nearby ice-shelves in Antarctica, 1986)
Keywords: Dronning Maud Land; NARE 1978/79; geofysikk; glasiologi; isshelf

Geophysical studies in the southern Weddell Sea - Haugland, Kristen; Kristoffersen, Yngve (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: NARE 1984/85; Sørishavet; Weddellhavet; geofysikk

På ekspedisjon til Sørpolen - Moberg, John (Norsk barneblad, 1985)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; ekspedisjoner; geofysikk; glasiologi; teknologi

Marine and non-marine contribution to the chemical composition of snow at the Riiser-Larsenisen Ice Shelf in Antarctica - Gjessing, Yngvar (Atmospheric Environment (1967), 1984)
The distribution with depth of seven different ions in three snow profiles, 1, 60 and 120km from the coast on Riiser-Larsenisen Ice Shelf (72° 30′ S, 15°E) shows a close co-variation between ions of marine origin and non-correlation between these ions and ions of presumptively non-marine origin. The deposition rates of ions of marine origin vary as 50:1 over some 120 km distance from the coast. The SO42−Na+ ratio in snow near the coast is lower than for bulk sea water indicating a loss of SO42− in snow to the atmosphere by volatilization.
Keywords: Dronning Maud Land; geofysikk; geokjemi; isshelf; meteorologi

The response of Antarctic icebergs to ocean waves - Wadhams, Peter; Kristensen, Monica; Orheim, Olav (Journal of Geophysical Research: Oceans, 1983)
The heave, tilt, and strain responses of three Antarctic tabular icebergs to ocean waves were measured during a 1980–1981 cruise of HMS Endurance to the South Atlantic. The three icebergs, located near the South Sandwich and South Orkney islands, were instrumented with accelerometers, tiltmeters, and wire strainmeters, while a Waverider buoy was used to record the ocean wave field. The thickness of the icebergs was surveyed by a helicopter-borne radio echo sounder. The heave response occurred mainly at the swell period but with outbreaks of bobbing which lasted for a few cycles at a resonant period (about 40 s), which agreed well with the predictions of a numerical finite element model. The roll response occurred mainly at a long resonant period (40–50 s), which again agreed well with the model, but there was also a significant response at ocean wave periods (5–20 s), which exceeded predictions. The strain response had a component at very long periods, which is unexplained by theory, while the surface strain at ocean wave periods agreed with the simple analytical model of Goodman et al. (1980). Using this model it is possible to predict a wave height and period that will cause breakup of the icebergs, and we conclude that swell-induced breakup is likely to occur during major storms in the open southern ocean.
Keywords: Sør-Orknøyene; Sørishavet; brehylle; geofysikk; glasiologi; havbølger; isberg; isbreer; isbrem; isfjell; isshelf; oseanografi

A microearthquake survey of Bouvet Island, South Atlantic - Kristoffersen, Yngve; Bungum, Hilmar (Tectonophysics, 1982)
A microearthquake survey carried out during the 1978–1979 Norwegian Antarctic Research Expedition indicates that only minor seismic activity is associated with the Bouvet volcano.
Keywords: Bouvetøya; NARE 1978/79; geofysikk; seismologi; vulkaner

Melting of ice in sea water: a primitive model with application to the Antarctic ice shelf and icebergs - Gade, Herman G. (Journal of Physical Oceanography, 1979)
Steady-state conditions are assumed to exist everywhere in the case of melting of the underside of an infinite slab of ice floating in sea water. Basic transfer equations for heat and salt are established and solutions derived for the interior corresponding to given far field values of the temperature and salinity of the water. The solutions are discussed in the T-S diagram where the behavior is particularly simple. Determining parameters are the characteristic velocities ks/d and Ks/h, where ks and Ks are the molecular and turbulent diffusivities, respectively, of salt, d and h the thicknesses of the corresponding laminar and turbulent layers. Also the nonmelting/nonfreezing case is discussed and the determining parameter established. Application of the theory to the Ross Ice Shelf (Little America V) gives acceptable results with d = 2 × 10−3 m and Ks = 20 −30 × 10−4 m2 s−1. Analysis of the static stability of the melt water mixtures reveals that with ambient temperatures approaching 17°C, the stratification becomes unstable. Icebergs brought to tropical waters will cause melt water mixtures to intrude at subsurface levels. Finally, convection obtained in laboratory experiments with melting ice in sea water is reported to be in concordance with the theoretically derived stability criterion.
Keywords: Sørishavet; geofysikk; glasiologi; hydrologi; oseanografi

Mesozoic palaeomagnetism in Vestfjella, Dronning Maud Land, East Antarctica - Løvlie, Reidar (Geophysical Journal of the Royal Astronomical Society, 1979)
Thermal and alternating field demagnetization of oriented samples of Mesozoic lava flows (200–230 Myr) and dykes (154–172 Myr) collected from seven nunataks within the Vestfjella region, Dronning Maud Land, revealed stable directions of magnetization of normal and reverse polarity. Directional distributions of both polarities define tight groups along the same palaeomagnetic axis. Depending on whether the regional westward dip of the lava flows originated prior to, or after the intrusive igneous phase, two or one, respectively, palaeomagnetic pole(s) can be estimated. Both poles, however, are in general accord with previous Mesozoic poles from East Antarctica.
Keywords: Dronning Maud Land; NARE 1976/77; geofysikk; geologi

Glaciological studies in the South Shetland Islands - Orheim, Olav (Antarctic Journal of the United States, 1974)
Keywords: Antarktis; Sør-Shetlandsøyene; geofysikk; glasiologi

Retrieval of current meters and study of thermohaline convection in the Weddell Sea - Bø, Redair; Foldvik, Arne; Kvinge, Thor (Antarctic Journal of the United States, 1973)
Keywords: Sørishavet; Weddellhavet; geofysikk; oseanografi

Innsjøer under isen i Antarktis - Fægri, Knut (Naturen, 1973)
Keywords: Antarktis; geofysikk; glasiologi

Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970 - Adie, Raymond J. (International Union of Geological Sciences, 1972)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

The sedimentary and volcanic sequence of Vestfjella, Dronning Maud Land - Hjelle, Audun; Winsnes, Thore S. (Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970, organized by the Scientific Committee on Antarctic Rsearch and sponsored by the International Union of Geological Sciences, 1972)
An area approximately 130 km long and 10-30 km wide along the inner part of the ice shelf in westernmost Dronning Maud Land is described. The nunataks which rise to a maximum of 1,132 m consist essentially of uniform basalt flows dipping slightly towards the west. These volcanic rocks are cut by an olivine-gabbro intrusion and several dykes and sills of Jurassic dolerite. Almost horizontal Lower Permian Beacon Supergroup sediments were found at one locality, about 20 km from the main range. There is no definite evidence that the volcanic rocks are younger than the Permian sediments; however, the chemical similarity with associated Jurassic dolerites and the general resemblance to Jurassic basalts in adjacent areas suggest that the Vestfjella volcanic rocks are also Jurassic age.
Keywords: Dronning Maud Land; geofysikk; geologi; sedimentologi

Deception: Sydpollandets aktive vulkan - Orheim, Olav (Polarboken, 1972)
Keywords: Sørishavet; geofysikk

Report on attendance at the Second Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6 to 15 August, 1970 - Kent, L E (Geological Survey of South Africa, 1971)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Abstracts of papers presented at Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6-15 August 1970 (SCAR/IUGS, 1970)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Cruise reports. International Weddell Sea Oceanographic Expedition : conducted onboard USCGC GLACIER (WAGB-4) - Kvinge, Thor (University of Bergen, 1970)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; fysisk oseanografi; geofysikk; oseanografi

Antarktis uten ispanser - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; geofysikk; geologi

Ny øy ved Deception (Polarboken, 1968)
Keywords: Sørishavet; geofysikk

Die "Brategg"-Expedition - Schubert, Kurt (Polarforschung, 1948)
Keywords: Peter I. Øy; Sørishavet; ekspedisjoner; geofysikk

Nomenclature of the submarine features of the southern seas - Mosby, Håkon (Report of the Committee on the Criteria and Nomenclature of the Major Divisions of the Ocean Bottom, 1939)
Keywords: Sørishavet; geofysikk; oseanografi; topografi